An analysis of alcohol compression ignition strategies on different engine platforms - Brian Gainey; Benjamin Lawler; Ankur Bhatt; Kunal Vedpathak; Sebastian Verhelst; Quinten Dejaegere; Martin Tunér; Adam Dempsey; Jared Zeman; Tyler Johnston; Musharrat Chowdhury; Sanguk Lee; et al. (Fuel, 2026)

Examining the Nuna-Rodinia supercontinent cycle in East Antarctica and testing correlations to the southwest United States: evidence from the Read Group (Shackleton Range) and the Nimrod Complex - Joe H. Metcalfe; Teal R. Riley; Michael J. Flowerdew; Nicholas J. Gardiner; Sebastian Fischer; Ian L. Millar; Joshua M. Garber; Maurice Brodbeck; David van Acken; Cristina Talavera; Heejin Jeon; Martin J. Whitehouse (Precambrian Research, 2026)

A protocol of tick quantification to obtain an indicator of individual resistance to infestation by Rhipicephalus (Boophilus) microplus in Brangus cattle - Martin Bonamy; M. Victoria Rossner; Sebastian Munilla; Macarena Sarli; Viviana Gomez; Stewart Kambo; Nicolas Morel; Guillermo Giovambattista; Santiago Nava (Preventive Veterinary Medicine, 2026)

Country-specific effects of organic viticulture on biodiversity and pest control - Jo Marie Reiff; Sebastian Kolb; Emilio Benítez; Rafael Alcalá Herrera; Stefan Möth; Adrien Rusch; Silvia Winter; Christoph Hoffmann; Martin H. Entling (Agriculture, Ecosystems & Environment, 2026)

Late Quaternary environments of Nicholas Swamp, Nicholas Range, eastern Tasmania/Lutruwita, Australia - Patrick T. Moss; Amirah Farrell; Sebastian Martin-Wallace; Peter D. McIntosh; Adrian Slee; Quan Hua; Kevin Welsh; Khairun Nisha Mohamed Ramdzan (Quaternary International, 2026)

Assessment of EnMAP data quality through global product validation activities - Maximilian Brell; Philipp Reiners; Luis Guanter; Karl Segl; Sabine Chabrillat; Daniel Scheffler; Mariana A. Soppa; Niklas Bohn; Javier Gorrono; Alexander Kokhanovsky; Astrid Bracher; Martin Bachmann; et al. (Remote Sensing of Environment, 2026)

Genome sizes and chromosomal repatterning in the evolution of Saxifraga and other Saxifragaceae - Natalia Tkach; Sebastian Spielau; David Horák; Martin Röser (Plant Systematics and Evolution, 2026)
The genus Saxifraga comprises ca. 480 species and is a characteristic element of mountainous and boreal to subpolar vegetation, particularly in the Northern Hemisphere. It comprises primarily perennial herbaceous plants that often form leaf rosettes and frequently have colorful, insect-pollinated flowers. This study used flow cytometry to estimate the genome sizes of saxifrage species on a broader taxonomic scale, identifying the total range of variation within the genus and its many infrageneric phylogenetic lineages. Measurements were made for 122 species, representing most of the infrageneric groups. Holoploid genome sizes (2C values) exhibited approximately 17-fold variation, whereas monoploid genome sizes (1Cx values) varied slightly less. The highest values were found in the predominantly Himalayan-Tibetan section Ciliatae , while the smallest were in the southern European subsection Arachnoideae . The genome size data were analyzed alongside karyological information, including chromosome numbers, polyploidy, changes in the chromosome base numbers ( x = 8–14) and aneuploidy. The potential evolutionary patterns of chromosome and genome differentiation among the main lineages of Saxifraga were analyzed, and possible relationships of genome size with life form, morphology, habitat, ecology, and biogeography were outlined. Additional data were presented for five other Saxifragaceae genera. All the data were used together to evaluate the potential evolution of chromosome base number in Saxifraga and the entire family Saxifragaceae. Additionally, an updated infrageneric classification of Saxifraga was introduced, including the newly designated subsection Irriguae .

Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Examining the lived experience of disability inclusion in physical education: the case for participatory research - Janine Coates; Lesley Sharpe; Carolynne Mason; Sebastian Ruin; Martin Giese (German Journal of Exercise and Sport Research, 2026)
Children and young people with disabilities have long been marginalized in research on physical education (PE), resulting in knowledge shaped largely by ableist assumptions and researcher-led agendas. This paper advocates participatory research to center children’s lived, embodied experiences and challenge epistemic injustice in PE scholarship. Grounded in rights-based principles, participatory approaches promote research with rather than on young people, recognizing them as competent social actors and knowledge producers. We examine the theoretical foundations of participatory methodologies, highlighting their commitment to inclusion, agency, collaboration, and contextualized knowledge. The paper outlines key components of participatory action research, including building relationships, co-constructing research aims, designing accessible methods, collaborative analysis, and action-focused dissemination. Attention is given to redistributing power within the researcher–participant dynamic and responding creatively to the diverse needs of young people with disabilities. A worked example from a special school illustrates how participatory approaches can foreground the perspectives of young people with learning and physical disabilities, generate context-specific insights, and influence action. We conclude by arguing that participatory research is not merely a method but an orientation toward social justice in PE research, requiring reflexivity, humility, and a willingness to embrace the “messiness” of genuinely inclusive inquiry.

Clinical-pharmacological medication reviews for insurants of a German statutory health insurance fund (Kaufmännische Krankenkasse (KKH)): a 5-year retrospective analysis (2019–2023) - Johannes Heck; Dirk O. Stichtenoth; Lutz Herbarth; Christoph Schröder; Ruxandra Sabau; Thorben Pape; Sebastian Schröder; Benjamin Krichevsky; Martin Schulze Westhoff; Martin Klietz; Stephan Greten; Patrick-Pascal Strunz; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
This study sought to evaluate the characteristics of clinical-pharmacological (CP) medication reviews conducted by the Institute for Clinical Pharmacology of Hannover Medical School for older, multimorbid, polymedicated insurants of the German statutory health insurance fund Kaufmännische Krankenkasse (KKH). Special emphasis was put on potential sex-specific differences between female and male insurants, prescriptions of potentially inappropriate medications for older individuals (PIMs), and potentially inappropriate duplicate prescriptions (PIDPs). Medication reviews conducted for KKH insurants between 2019 and 2023 ( n = 334) were analyzed retrospectively. Clinical trial number is not applicable. The median age of KKH insurants (58.1% female) was 74 years (first quartile (Q1): 68; third quartile (Q3): 80). Insurants displayed a median of 7 diseases (Q1: 5; Q3: 9) and took a median of 13 drugs (Q1: 11; Q3: 16). A median of 4 CP recommendations was issued per medication review (Q1: 3; Q3: 5). The number of CP recommendations was significantly higher for female compared to male insurants (median of 4 (Q1: 3; Q3: 6) vs. median of 3 recommendations (Q1: 2; Q3: 4); p < 0.001), while the number of drugs was identical and the number of diagnoses was higher for female insurants. The most frequently prescribed PIMs were tricyclic antidepressants, benzodiazepines, and Z-drugs. At least one PIDP was detected in 16.5% of medication reviews. The sex-specific difference in the number of CP recommendations between female and male insurants may point to an unmet pharmacotherapeutic need in older women. PIM prescriptions and PIDPs were relevant topics of CP recommendations, suggesting possibilities for pharmacotherapeutic optimization in older, multimorbid, polymedicated patients.

Fate of persistent and mobile substances in drinking water treatment: A systematic comparison of treatment options - Pia Schumann; Luisa Rabe; Malte Zamzow; Isabelle Neuwald; Thomas P. Knepper; Matthias Muschket; Daniel Zahn; Pascal Hasselder; Thorsten Reemtsma; Martin Jekel; Aki Sebastian Ruhl (Journal of Hazardous Materials, 2026)

Typology of Agricultural Land Systems in Germany to Support Tailoring of Agri-Environmental Schemes to Reduce Pressures on Farmland Biodiversity - Martin Pingel; Diana Sietz; Norbert Röder; Sebastian Klimek; Burkhard Golla (Environmental Management, 2026)
Farmland biodiversity and associated ecosystem services are threatened by the expansion and intensification of agriculture. Despite substantial efforts, European conservation policies have largely failed to halt or reverse the decline of farmland biodiversity. To address the pressures associated with agricultural intensification more effectively, conservation measures - such as agri-environmental schemes – need to be tailored based on spatially explicit land system classifications that reflect the interdependencies between agricultural land use and biodiversity. In this study, we present a spatially explicit typology of agricultural land systems in Germany offering a meaningful generalization of the country’s agricultural landscapes to inform and support the tailoring of agri-environmental schemes. We applied a cluster analysis based on indicators of land cover, landscape structure, land-use intensity of different production systems, as well as biophysical indicators, such as climate and topography. Experts from agriculture, conservation, and administration sectors contributed to refining both the indicator selection and the clustering results. Clustering revealed eight distinct agricultural land system types in Germany, including arable cash crop-dominated, animal husbandry-dominated, and mosaic land-use agricultural land system types. Each type represents a characteristic combination of indicators, offering key insights into the specific pressures affecting farmland biodiversity. Drawing on this typology, we discuss entry points for tailoring agri-environmental schemes to reduce land system-specific pressures on biodiversity. This typology has the potential to increase the ecological effectiveness of agri-environmental schemes by tailoring them to land system-specific pressures. Moreover, the methodological approach can be adapted to other countries or scaled beyond the national level.

Effect-based methods and effect-based trigger values for estrogenicity monitoring in surface water: an interlaboratory study - Livia Gómez; Dimitar Marinov; Elena Porcel-Rodríguez; Diletta Scaccabarozzi; Isabella Sanseverino; Pietro Sciuto; Frank Narendja; Romana Hornek-Gausterer; Katharina Lenz; Carole Chalon; Yves Marneffe; Přemysl Soldán; et al. (Environmental Research, 2026)

Knowledge and uses of freshwater mussels in Europe - Noé Ferreira-Rodríguez; Ján Černecký; Jacek Dołęga; Ovidiu Drăgan; Anna Elmlund; Fabio Ercoli; Dariusz Halabowski; Martina Ilarri; Sandra Kaźmierczak; Anna Maria Labecka; Daniyar Memedemin; Monika Mioduchowska; et al. (Ambio, 2026)

Parasitic freshwater mussels impact the shoaling behaviour and habitat use of their host fish - Sebastian L. Rock; Fabio Tarena; Madeleine Blomqvist; Olle Calles; P. Anders Nilsson; Johan Watz; Martin Österling (Behavioral Ecology and Sociobiology, 2026)
Freshwater mussels in the order Unionida are a highly endangered taxon of ecosystem engineers with a variety of conservation and reintroduction efforts around the world attempting to increase wild populations. The unionid lifecycle involves a parasitic larval life-stage (glochidia), primarily adapted for dispersal rather than growth. Little is known about the behavioural effects of the glochidia on their host fish. We investigated the shoaling behaviour and habitat preference of the Eurasian minnow ( Phoxinus phoxinus ) while infested with the glochidia of one of Europe’s most endangered unionid mussels, the thick-shelled river mussel ( Unio crassus ). Behavioural assays were carried out in a hydrologically complex flow-through aquaria at two time points of the infestation period, a carrying stage and an excystment stage (14 and 28 days post infestation). We demonstrate that glochidiosis reduces minnow shoaling frequency and increases the number of isolated individuals. However, minnow shoal area and nearest neighbour distance remained unaffected. Infested minnows demonstrated a significant preference for slower flowing and less turbulent habitat. These results suggest that glochidiosis reduces host swimming efficiency, which likely increases predatory pressure on infested minnows. Simultaneously, this preference for calmer habitats may benefit the encysted mussels, as these habitats are better suited for juvenile mussel excystment. Our results highlight the importance of low-flow and low-turbulence habitats for unionid recruitment, as parasitized host individuals tolerate these conditions well.

Antimicrobial nano silver (Ag)-enabled wound dressing evaluated using open flow microperfusion: Comparison of uncoated versus hydroxyethyl cellulose-coated Ag - Ilaria Zanoni; Simon Schwingenschuh; Thomas Birngruber; Peter Reisenegger; Sandeep Keshavan; Sebastian Santhosh Martin; Bengt Fadeel; Kai Moritz Eder; Jürgen Schnekenburger; Alessandro Bonetto; Elena Badetti; Claudia Vineis; et al. (NanoImpact, 2026)

Development and Pre-clinical Feasibility of a Catheter-Based Platform for Interventional Phase−0 Drug Response Measurements - Sharath K. Bhagavatula; Ellen Maloney; Hidde Ploeger; Sebastian W. Ahn; Samantha Martin; Santhosh A. Mathew; Sajanlal Panikkanvalappil; Guigen Liu; Oliver Jonas (Annals of Biomedical Engineering, 2026)

Kriging prior regression: A case for kriging-based spatial features with TabPFN in soil mapping - Jonas Schmidinger; Viacheslav Barkov; Sebastian Vogel; Martin Atzmueller; Gerard B.M. Heuvelink (Computers and Electronics in Agriculture, 2026)

Forest Heterogeneity by Chain Saw: How Between‐Patch Variation in Old Growth Attributes Changes the Metacommunities of Beetles - Oliver Mitesser; Marc W. Cadotte; Akira S. Mori; Fons van der Plas; Anne Chao; Julia Rothacher; Claus Bässler; Mirjana Bevanda; Peter H. W. Biedermann; Pia Bradler; Antonio Castañeda‐Gómez; Orsi Decker; et al. (Ecology Letters, 2026)
Metacommunity theory has expanded our understanding of how spatial dynamics and local interactions influence species communities. Different assembly archetypes, reflecting different roles of species differences, habitat differences, and dispersal have been described, but we lack empirical studies specifically in terrestrial habitats testing which archetype is most important. In a replicated design, we experimentally enhanced structural between‐patch heterogeneity in homogeneous production forests and developed a statistical framework controlling for sample incompleteness to detect different metacommunity processes. Meta‐analyses on > 100 K individuals of > 1.3 K beetle species showed an increase of ~60 species in heterogenized forests at γ‐level promoted by increasing α‐diversity consistent with the mass‐effect and an increase of β‐diversity by ~10% supporting species‐sorting . Additionally, we tested β‐deviations from random assembly as a proxy of neutral processes . Findings indicate that enhancing structural heterogeneity can shift forests from patch‐dynamics dominance towards mass‐effect and species‐sorting , offering a promising pathway to restore biodiversity in managed landscapes.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

The Vitamin D Receptor Ortholog Hr96 Modulates Neuronal and Mitochondrial Dynamics in a Drosophila Model of Alzheimer’s Disease - Guilherme Gischkow Rucatti; Francisco Muñoz-Carvajal; Nicole Sanhueza; Sebastian Oyarce-Pezoa; Yesid Cuesta-Astroz; Leandro Murgas; Melissa Caru-Ruiz; Alberto J.M. Martin; Melissa Calegaro-Nassif; Carol D. SanMartín; Mario Sanhueza (Molecular Neurobiology, 2026)

Migration of cyclic dimethyl siloxanes from silicone elastomers into food – determination of D4 to D25 via on-line coupled HPLC-GC-FID - Martin Eckardt; Ann-Kathrin Seidel; Sebastian Säger; Thomas J. Simat (Food Additives & Contaminants: Part A, 2025)

Benchmarking CO₂ storage simulations: Results from the 11th Society of Petroleum Engineers Comparative Solution Project - Jan M. Nordbotten; Martin A. Fernø; Bernd Flemisch; Anthony R. Kovscek; Knut-Andreas Lie; Jakub W. Both; Olav Møyner; Tor Harald Sandve; Etienne Ahusborde; Sebastian Bauer; Zhangxing Chen; Holger Class; et al. (International Journal of Greenhouse Gas Control, 2025)

Petroleum-fuelled methanogenesis and microbial hydrocarbon oxidation at an abandoned oil well - Martin Blumenberg; Sebastian Jordan; Georg Scheeder; Martin Krüger; Stefan Schloemer (Applied Geochemistry, 2025)

Identification of a surface protein in the extracellular polymeric substances of seawater-adapted aerobic granular sludge - Le Min Chen; Tessa Hofstra; Jelle Langedijk; Sebastian Andrei; Martin Pabst; Mario Pronk; Mark C.M. van Loosdrecht; Yuemei Lin (Water Research, 2025)

Effect of air temperature, milk production and shearing on drinking water intake of Angora goats in pen during summer - Martin Calianno; Daniel A. Castillo; Santiago I. Hurtado; Saúl Deluchi; Brenda Garcia; Laura Villar; E. Sebastian Villagra; Marcos H. Easdale (Small Ruminant Research, 2025)

Coastal zones of the Baltic Sea in the Anthropocene: Current state and the impact of climate change - Maren Voss; Peter Holtermann; Soeren Ahmerkamp; Damian Leonardo Arévalo Martínez; Bronwyn Cahill; Manita Chouksey; Joachim W. Dippner; Jörg Dutz; Peter Feldens; Jacob Geersen; Kaja Gentsch; Mayya Gogina; et al. (Estuarine, Coastal and Shelf Science, 2025)

Metabarcoding reveals time after tree death as main driver of diversity and composition of invertebrate communities in deadwood - Leah Vogelfänger; Wolfgang W. Weisser; Martin M. Gossner; Jérôme Morinière; Daniel Rieker; Peter Schall; Christian Ammer; Sebastian Seibold (Forest Ecology and Management, 2025)

Results of the SSM-SICOPS melt tests of the EU-SAFEST project - Gert Langrock; Torsten Keim; Manfred Fischer; Matthias Braun; Sebastian Kohn; Roland Hofmann; Rainer Bezold; Martin Neumeister; Sevostian Bechta; Patrick Isaksson (Annals of Nuclear Energy, 2025)

Riparian and aquatic organisms respond differently to altered hydrology and Bacillus thuringiensis israelensis (Bti) application in floodplain mesocosms - Peer Bauspiess; Martin H. Entling; Tanja J. Joschko; Sebastian Kolb; Alanah Kripp; Marlene Schäffer; Hanna C. Schleihauf; Agnes Schöndorfer; Ralf Schulz; Jens Schirmel (Aquatic Sciences, 2025)
Floodplains are habitats with an outstanding biodiversity but have been strongly affected by anthropogenic activities such as channelization and bank enforcement. The remaining floodplains are impacted by climate change-driven alterations in the hydrological regime and by chemical stressors. However, the extent and interactive effects of these stressors are not well understood, especially in small-scale floodplains. In a mesocosm experiment, we therefore studied aquatic and riparian (floodplain) invertebrate communities in response to changes in the hydrological regime as predicted by climate change and the application of the biocide Bacillus thuringiensis israelensis (Bti). The mesocosm facility contained 12 separated floodplain mesocosms. The control hydrological regime consisted of a 40-cm water level and one monthly flood throughout the year, while the altered hydrological regime (scenario) had weekly floods during winter and a lower water level during summer. In addition, half of both the control and scenario floodplain mesocosms were treated with Bti at the maximum field rate applied for mosquito control. We found that the hydrological regime had contrasting effects for the aquatic and riparian communities. While the number of individuals of most aquatic invertebrates decreased in the scenario floodplain mesocosms, we found predominantly higher number of individuals of riparian arthropods. Furthermore, Bti had negative effects on some nontarget organisms, such as ground beetles and mayflies, and interacted with the hydrological regime in some cases. We conclude that the effects of both hydrological regime and Bti are taxa-dependent and that the hydrological regime revealed opposing effects between aquatic and riparian habitats.

A global meta‐analysis of ecological functions and regulating ecosystem services of freshwater bivalves - Alexandra Zieritz; Joshua I. Brian; Ronaldo Sousa; David C. Aldridge; Carla L. Atkinson; Karel Douda; Caryn Vaughn; Yulia Bespalaya; Tabitha Richmond; Adam M. Ćmiel; Alma Crisp; Andreas H. Dobler; et al. (Limnology and Oceanography, 2025)
Freshwater bivalves are globally distributed, diverse, and common in benthic communities. Many taxa, particularly in the most species‐rich order, Unionida, are declining due to anthropogenic stressors, while a small number of non‐native species have become increasingly abundant and widespread, commonly replacing native bivalve assemblages. To understand how these global changes may impact ecosystems and people, we conducted a meta‐analysis of existing literature quantifying the ecological functions (= supporting or intermediate ecosystem services) and regulating ecosystem services of freshwater bivalves (hereafter “ecosystem services”). Random effects meta‐analysis modeling across 447 case studies revealed a positive effect on human health, safety, or comfort of freshwater bivalve ecosystem services overall and specifically, via effects on native macrofauna, microorganisms, wastes, and pollutants, and the physico‐chemical condition or quantity of sediments. Generally, effects of native species and species within the orders Unionida and Venerida were more significant and positive than those of other freshwater bivalves. No significant overall effect was found for ecosystem services related to zooplankton, algae, invasive species, and the physico‐chemical condition of ambient water. Moreover, a significant bias toward publication of positive results existed for studies quantifying ecosystem services related to algae. These findings illustrate the global importance of the ecosystem services of freshwater bivalves and highlight the need for large‐scale conservation and restoration efforts for their species and populations globally, including those of common species. Our findings also question common assumptions of strong and ubiquitous effects of freshwater bivalves on algae and water condition, cautioning against extrapolating observations across systems.

Leaf litter material limits the elimination of organic micropollutants in redox-differentiated lab-scale bank filtration columns - Jimmy Köpke; Uranchimeg Bayarsaikhan; Lorenz Adrian; Martin Jekel; Aki Sebastian Ruhl (Science of The Total Environment, 2025)

Porosity and hydrous alteration of the Martian crust from InSight seismic data - Brigitte Knapmeyer-Endrun; Ludmila Adam; Sebastian Carrasco; Matthew P. Golombek; Doyeon Kim; Martin Knapmeyer; Katarina Miljković; Ana-Catalina Plesa; Nicholas H. Warner; Mark Wieczorek (Physics of the Earth and Planetary Interiors, 2025)

Diversity in Resource Use Strategies Promotes Productivity in Young Planted Tree Species Mixtures - Joel Jensen; Haben Blondeel; Joannès Guillemot; Florian Schnabel; Hernán Serrano‐León; Harald Auge; Lander Baeten; Nadia Barsoum; Jürgen Bauhus; Christel Baum; Raimundo Bermudez; Friderike Beyer; et al. (Global Change Biology, 2025)
Mixed‐species forestry is a promising approach to enhance productivity, increase carbon sequestration, and mitigate climate change. Diverse forests, composed of species with varying structures and functional trait profiles, may have higher functional and structural diversity, which are attributes relevant to a number of mechanisms that can influence productivity. However, it remains unclear whether the context‐dependent roles of functional identity, functional diversity, and structural diversity can lead to a generalized understanding of tree diversity effects on stand productivity. To address these gaps, we analyzed growth data from 83,600 trees from 89 species across 21 young tree diversity experiments spanning five continents and three biomes. Results revealed a positive saturating relationship between tree species richness and stand productivity, with reduced variability in growth rates among more diverse stands. Structural equation modeling demonstrated that functional diversity mediated the positive effects of species richness on productivity. We additionally report a negative relationship between structural diversity and productivity, which decreased with increasing species richness. When partitioning net diversity effects, we found that selection effects played a dominant role in driving the overall increase in productivity in these predominantly young stands, contributing 77% of the net diversity effect. Selection effects increased with diversity in wood density. Furthermore, acquisitive species with lower wood density and higher leaf nitrogen content had higher productivity in more diverse stands, while conservative species showed neutral to slightly negative responses to species mixing. Together, these results suggest that combining acquisitive with conservative species allows acquisitive species to drive positive selection effects while conservative species tolerate competition. Thus, contrasting resource‐use strategies can enhance productivity to optimize mixed‐species forestry, with potential for both ecological and economic benefits.

Exercise therapy innovations in outpatient mental health care - David Victor Fiedler; Stephanie Rosenstiel; Stefan Peters; Anna Lena Flagmeier; Lena Zwanzleitner; Leonie Sundmacher; Ander Ramos-Murguialday; Martin Hautzinger; Thomas Ehring; Sebastian Wolf; Gorden Sudeck (German Journal of Exercise and Sport Research, 2025)
For successful implementation of healthcare interventions, attitudes of healthcare professionals are a key factor. Research in the field of psychological treatment suggests that attitude towards evidence-based practice (EBP) may play a crucial role. However, little research has been conducted on the extent to which this applies to the field of exercise therapy, where there is a strong need for development regarding the dissemination of EBP. A recent pragmatic multisite randomized controlled trial (ImPuls) can serve as an innovative example for the implementation of an evidence-based exercise intervention including behavior change techniques within the outpatient mental health care system in Germany. The aim of the current study was to explore the role of exercise therapists’ attitude towards EBP for an implementation process by identifying relationships with other factors of importance for implementing innovations (e.g., motivation or self-efficacy). Exercise therapists ( n = 26) completed online surveys pre- (week 0) and postintervention (week 24+). Correlation analyses and linear regressions were performed considering a total score for attitude towards EBP as well as mean scores for its subdimensions. The total score was rather positive (mean = 2.58, standard deviation = 0.43) and significantly related to program-specific motivation ( r = 0.64, p < 0.001), self-efficacy ( r = 0.42, p < 0.034), and acceptance ( r = 0.56, p < 0.003) at baseline. Exercise therapists’ education and further training should therefore have an increased focus on EBP, including the usage of scientific findings, the integration into routine practice and the scopes and obligations that come along with it.

Understanding the dynamic interplay of CH4/CO2 ratio in electrified reforming of biogas to renewable methanol production: A pilot plant story - Thomas N. From; Marené Rautenbach; Behzad Partoon; Martin Østberg; Sebastian T. Wismann; Anders Bentien; Peter M. Mortensen (Chemical Engineering Journal, 2025)

Effects of land cover and protected areas on flying insect diversity - James S. Sinclair; Dominik Buchner; Mark O. Gessner; Jörg Müller; Steffen U. Pauls; Stefan Stoll; Ellen A. R. Welti; Claus Bässler; Jörn Buse; Frank Dziock; Julian Enss; Thomas Hörren; et al. (Conservation Biology, 2025)
Widespread insect losses are a critical global problem. Mitigating this problem requires identifying the principal drivers across different taxa and determining which insects are covered by protected areas. However, doing so is hindered by missing information on most species owing to extremely high insect diversity and difficulties in morphological identification. To address this knowledge gap, we used one of the most comprehensive insect DNA metabarcoding data sets assembled (encompassing 31,846 flying insect species) in which data were collected from a network of 75 Malaise traps distributed across Germany. Collection sites encompass gradients of land cover, weather, and climate, along with differences in site protection status, which allowed us to gain broader insights into how insects respond to these factors. We examined changes in total insect biomass, species richness, temporal turnover, and shifts in the composition of taxa, key functional groups (pollinators, threatened species, and invasive species), and feeding traits. Lower insect biomass generally equated to lower richness of all insects and higher temporal turnover, suggesting that biomass loss translates to biodiversity loss and less stable communities. Spatial variability in insect biomass and composition was primarily driven by land cover, rather than weather or climate change. As vegetation and land‐cover heterogeneity increased, insect biomass increased by 50% in 2019 and 56% in 2020 and total species richness by 58% and 33%, respectively. Similarly, areas with low‐vegetation habitats exhibited the highest richness of key taxa, including pollinators and threatened species, and the widest variety of feeding traits. However, these habitats tended to be less protected despite their higher diversity. Our results highlight the value of heterogeneous low vegetation for promoting overall insect biomass and diversity and that better protection of insects requires improved protection and management of unforested areas, where many biodiversity hotspots and key taxa occur.

Biological methane removal by groundwater trickling biofiltration for emissions reduction - Francesc Corbera-Rubio; Alje S. Boersma; Weren de Vet; Martin Pabst; Paul W.J.J. van der Wielen; Maartje A.H.J. van Kessel; Mark C.M. van Loosdrecht; Doris van Halem; Sebastian Lücker; Michele Laureni (Water Research, 2025)

Comparison of NO2 diffusion tube measurement methods and related uncertainties - David Medland; Gabriel Garcia; Tom Gardiner; Nicholas A. Martin; Valerio Ferracci; Ashley Wilkins; David Fryer; Tom Holmes; Pete Edwards; Sebastian Diez; David Butterfield (Atmospheric Environment, 2025)

The control of physical and biological drivers on pelagic methane fluxes in a Patagonian fjord (Golfo Almirante Montt, Chile) - Oliver Schmale; Volker Mohrholz; Svenja Papenmeier; Klaus Jürgens; Martin Blumenberg; Peter Feldens; Sebastian Jordan; Paula Ruiz-Fernández; Christian Meeske; Jenny Fabian; Sören Iwe; Lars Umlauf (Science of The Total Environment, 2025)

Discussion on the validity of commonly used reliability indices in sports medicine and exercise science: a critical review with data simulations - Konstantin Warneke; Thomas Gronwald; Sebastian Wallot; Alessia Magno; Martin Hillebrecht; Klaus Wirth (European Journal of Applied Physiology, 2025)
Apart from objectivity and validity, reliability is considered a precondition for testing within scientific works, as unreliable testing protocols limit conclusions, especially for practical application. Classification guidelines commonly refer to relative reliability, focusing on Pearson correlation coefficients ( r p ) and intraclass correlation coefficients (ICC). On those, the standard error of measurement (SEM) and the minimal detectable change (MDC) are often calculated in addition to the variability coefficient (CV). These, however, do not account for systematic or random errors (e.g., standardization problems). To illustrate, we applied common reliability statistics in sports science on simulated data which extended the sample size of two original counter-movement-jump sessions from (youth) elite basketball players. These show that excellent r p and ICC (≥ 0.9) without a systematic bias were accompanied by a mean absolute percentage error of over 20%. Furthermore, we showed that the ICC does not account for systematic errors and has only limited value for accuracy, which can cause misleading conclusions of data. While a simple re-organization of data caused an improvement in relative reliability and reduced limits of agreement meaningfully, systematic errors occurred. This example underlines the lack of validity and objectivity of commonly used ICC-based reliability statistics (SEM, MDC) to quantify the primary and secondary variance sources. After revealing several caveats in the literature (e.g., neglecting of the systematic and random error or not distinguishing between protocol and device reliability), we suggest a methodological approach to provide reliable data collections as a precondition for valid conclusions by, e.g., recommending pre-set acceptable measurement errors.

Reconstructing past sea-level changes from storm-built beach ridges - Alessio Rovere; Marta Pappalardo; Sebastian Richiano; Deirdre D. Ryan; Karla Rubio-Sandoval; Patricio Martin Ruiz; Alejandro Montes; Evan J. Gowan (Geomorphology, 2025)

A silicon-membrane based artificial feeding system for Amblyomma sculptum nymphs - Anna Obiegala; Nina Król; Lara M. I. Heyse; Martin Pfeffer; Martina Montini; Santiago Nava; Patrick S. Sebastian (Experimental and Applied Acarology, 2025)

Errichtung des Schwallausgleichsbeckens Silz - Sebastian Perzlmaier; Martin Oberwalder (WASSERWIRTSCHAFT, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Action against invasive species: Knowledge, effect and behavioural drivers of fall armyworm management - Martin Paul Jr. Tabe-Ojong; Yong Sebastian Nyam (Ecological Economics, 2025)

Scheduling Optimization of a Compact End-to-End Pharmaceutical Manufacturing Line: Design and Experimental Evaluation - Sebastian Knoll; Martin Steinberger; Lisa Kuchler; Atabak Azimi; Markus Tranninger; Stephan Sacher; Martin Horn (Journal of Pharmaceutical Innovation, 2025)
In today’s competitive landscape, the demand for scheduling optimization to enhance processes and industrial plants is rapidly increasing. To address this need, we introduce a scheduling optimization approach for a compact continuous pharmaceutical manufacturing line by developing a mixed integer linear programming (MILP) model that incorporates all necessary constraints and bounds. The MILP employs a continuous time representation and an extension to a multi-product manufacturing line to improve the capabilities of current equipment and the model itself is shown. To reinforce the ideas and exemplify the overall concept, we present simulation results, demonstrating the optimal scheduling plans for various scenarios. In a case study, we applied the MILP to a manufacturing line and successfully integrated the optimal scheduling plan into the plant. Our results show that the time constraints, expected mass flows, and mass hold-ups align with those of the optimal scheduling plan, confirming that fully automated and integrated operations are feasible.

Can triad forestry reconcile Europe’s biodiversity and forestry strategies? A critical evaluation of forest zoning - Thomas A. Nagel; Mariano Rodríguez-Recio; Tuomas Aakala; Per Angelstam; Admir Avdagić; Zbigniew Borowski; Andrés Bravo-Oviedo; Gediminas Brazaitis; Thomas Campagnaro; Michał Ciach; Milic Curovic; Inken Doerfler; et al. (Ambio, 2025)
Balancing increasing demand for wood products while also maintaining forest biodiversity is a paramount challenge. Europe’s Biodiversity and Forest Strategies for 2030 attempt to address this challenge. Together, they call for strict protection of 10% of land area, including all primary and old growth forests, increasing use of ecological forestry, and less reliance on monocultural plantations. Using data on country wide silvicultural practices and a new database on strict forest reserves across Europe, we assess how triad forest zoning could help meet these goals. Our analysis reveals that zoning in Europe is overwhelmingly focused on wood production, while there has been little concomitant protection of forests in strict reserves. Moreover, most strict forest reserves are

Mass accumulation rates decreased in the Skagerrak basin over the last 100 years - Timo Spiegel; Andrew W. Dale; Nina Lenz; Mark Schmidt; Matthias Moros; Sebastian Lindhorst; Hendrik Wolschke; Daniel Müller; Martin Butzin; Michael Fuhr; Habeeb Thanveer Kalapurakkal; Sabine Kasten; et al. (Continental Shelf Research, 2025)

Sport.developments—physical activity and sport in our society from a socioeconomic perspective - Martin Schnitzer; Michael Barth; Sebastian Kaiser (German Journal of Exercise and Sport Research, 2025)

Operator exposure and cabin protection in plant protection product application - Gabor Molnar; Katrin Ahrens; Jens Karl Wegener; Sebastian Dittmar; Enrico Peter; Sabine Martin; Jan-Niklas Schäckermann; Markus Röver (Journal of Consumer Protection and Food Safety, 2025)
Tightly sealed driver's cabs can effectively protect the user from exposure when applying crop protection products. Therefore, under certain conditions, users in such cabins can avoid wearing personal protective equipment for skin and eyes. The protective effect depends on the technical design and handling of the different cabin types and can be divided into categories with different levels of protection. Since the level of protection of the different types of cabins and the associated possibility of not wearing personal protective equipment has not been sufficiently scientifically verified in the past, the present study was carried out to close this gap. Field and laboratory test methods were developed and used to assess exposure levels. External contamination of the cabin was measured using various dosimeters. Exposure inside the cabins was measured on coveralls and gloves to measure dermal exposure and with aerosol sampling pumps to determine inhalation exposure. Tests were conducted on tractors with different cab categories using an air-assisted orchard sprayer as a worst-case scenario for exposure to spray drift. Additionally, an alternative laboratory test method was developed and conducted to evaluate filter efficiency under controlled conditions and compare it with the field tests. The results showed that exposure inside closed cabins was generally low and was not notably correlated with the cabin category. All types of cabins tested were found to provide significant protection from dermal and inhalation exposure.

Validation of the spray drift modeling software AGDISPpro applied to remotely piloted aerial application systems - Sebastian Castro-Tanzi; Michael Winchell; Zhenxu Tang; Milton E. Teske; Glen R. Whitehouse; Brad Fritz; Dan Martin (Science of The Total Environment, 2025)

bneR: A collaborative workflow for air pollution exposure modeling and uncertainty characterization using the Bayesian Nonparametric Ensemble - Jaime Benavides; Carlos Carrillo-Gallegos; Vijay Kumar; Sebastian T. Rowland; Lawrence G. Chillrud; Temilayo Adeyeye; John Paisley; Brent Coull; Daven K. Henze; Randall V. Martin; Arlene M. Fiore; Marianthi-Anna Kioumourtzoglou (Journal of Environmental Management, 2025)

The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Investigation of the combustion characteristics and knock tendencies of neat C1–C4 alcohol fuels using a CFR engine - André L. Olson; Martin Tunér; Sebastian Verhelst (Fuel, 2025)

Perfluorodecanoic acid (PFDA) increases oxidative stress through inhibition of mitochondrial β-oxidation - Raimund Widhalm; Sebastian Granitzer; Benjamin Natha; Ottavia Zoboli; Julia Derx; Harald Zeisler; Hans Salzer; Stefan Weiss; Nicole Schmitner; Robin A. Kimmel; Tamina Österreicher; Raimund Oberle; et al. (Environmental Pollution, 2025)

Enhancing heat pump performance for domestic hot water preparation: A comparative analysis in existing multi-family houses - Michael Kropp; Manuel Lämmle; Sebastian Herkel; Hans-Martin Henning; Andreas Velte-Schäfer (Energy and Buildings, 2025)

Adaptive variation in opsin expression of sticklebacks from different photic habitats - Theo C. M. Bakker; Meike Hiermes; Björn Müller; Sebastian Martin; Diana J. Rennison; Ingolf P. Rick (Hydrobiologia, 2025)
We studied phenotypic and genetic adaptation of the visual system of three-spined sticklebacks, Gasterosteus aculeatus , from North Uist, Scotland. We quantified differences in opsin gene expression of the four cone opsin genes among wild-caught fish from three lakes with clear and from three with tea-stained water and their offspring that were raised in clear water. In addition, visual sensitivity of wild-caught fish was modelled from opsin expression levels. Wild-caught fish from tea-stained waters had a lower SWS1 proportional expression than fish from clear waters, a difference that tended to be maintained in lab-bred fish. Compared to lab-bred fish, wild-caught fish had a higher SWS1 but lower SWS2 proportional expression independent of water clarity. For RH2 and LWS there were significant interactions between generation and water clarity. Reproductively mature fish had a higher LWS but lower proportional expression of RH2 than non-reproductive fish. Sex did not have a significant effect on expression. There was a significant positive association and, depending on chromophore ratio, a distinct match between the centre wavelengths, used as a proxy for spectral distribution, of ambient habitat light and spectral sensitivity indicating that the visual system of sticklebacks is tuned to their local light environment, suggesting adaptation.

Evaluating the performance of multi-omics integration: a thyroid toxicity case study - Sebastian Canzler; Kristin Schubert; Ulrike E. Rolle-Kampczyk; Zhipeng Wang; Stephan Schreiber; Hervé Seitz; Sophie Mockly; Hennicke Kamp; Volker Haake; Maike Huisinga; Martin von Bergen; Roland Buesen; et al. (Archives of Toxicology, 2025)
Multi-omics data integration has been repeatedly discussed as the way forward to more comprehensively cover the molecular responses of cells or organisms to chemical exposure in systems toxicology and regulatory risk assessment. In Canzler et al. (Arch Toxicol 94(2):371–388. https://doi.org/10.1007/s00204-020-02656-y ), we reviewed the state of the art in applying multi-omics approaches in toxicological research and chemical risk assessment. We developed best practices for the experimental design of multi-omics studies, omics data acquisition, and subsequent omics data integration. We found that multi-omics data sets for toxicological research questions were generally rare, with no data sets comprising more than two omics layers adhering to these best practices. Due to these limitations, we could not fully assess the benefits of different data integration approaches or quantitatively evaluate the contribution of various omics layers for toxicological research questions. Here, we report on a multi-omics study on thyroid toxicity that we conducted in compliance with these best practices. We induced direct and indirect thyroid toxicity through Propylthiouracil (PTU) and Phenytoin, respectively, in a 28-day plus 14-day recovery oral rat toxicity study. We collected clinical and histopathological data and six omics layers, including the long and short transcriptome, proteome, phosphoproteome, and metabolome from plasma, thyroid, and liver. We demonstrate that the multi-omics approach is superior to single-omics in detecting responses at the regulatory pathway level. We also show how combining omics data with clinical and histopathological parameters facilitates the interpretation of the data. Furthermore, we illustrate how multi-omics integration can hint at the involvement of non-coding RNAs in post-transcriptional regulation. Also, we show that multi-omics facilitates grouping, and we assess how much information individual and combinations of omics layers contribute to this approach.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Opportunities and challenges of using human excreta-derived fertilizers in agriculture: A review of suitability, environmental impact and societal acceptance - Sarah van den Broek; Inna Nybom; Martin Hartmann; Sebastian Doetterl; Gina Garland (Science of The Total Environment, 2024)

Corrigendum to “Generation, characterization, and toxicological assessment of reference ultrafine soot particles with different organic content for inhalation toxicological studies” [Sci. Total Environ. Volume 951 (2024) 175727] - Anusmita Das; Jana Pantzke; Seongho Jeong; Elena Hartner; Elias J. Zimmermann; Nadine Gawlitta; Svenja Offer; Deeksha Shukla; Anja Huber; Narges Rastak; Arūnas Meščeriakovas; Natalia P. Ivleva; et al. (Science of The Total Environment, 2024)

The EnMAP spaceborne imaging spectroscopy mission: Initial scientific results two years after launch - Sabine Chabrillat; Saskia Foerster; Karl Segl; Alison Beamish; Maximilian Brell; Saeid Asadzadeh; Robert Milewski; Kathrin J. Ward; Arlena Brosinsky; Katrin Koch; Daniel Scheffler; Stephane Guillaso; et al. (Remote Sensing of Environment, 2024)

The last of their kind: Is the genus Scutiger (Anura: Megophryidae) a relict element of the paleo-Transhimalaya biota? - Sylvia Hofmann; Lars Podsiadlowski; Tobias Andermann; Michael Matschiner; Chitra B. Baniya; Spartak N. Litvinchuk; Sebastian Martin; Rafaqat Masroor; Jianhuan Yang; Yuchi Zheng; Daniel Jablonski; Joachim Schmidt (Molecular Phylogenetics and Evolution, 2024)

One to rule them all? Assessing the performance of sustainable forest management indicators against multitaxonomic data for biodiversity conservation - Yoan Paillet; Livia Zapponi; Peter Schall; Jean-Matthieu Monnet; Christian Ammer; Lorenzo Balducci; Steffen Boch; Gediminas Brazaitis; Alessandro Campanaro; Francesco Chianucci; Inken Doerfler; Markus Fischer; et al. (Biological Conservation, 2024)

Can isometric testing substitute for the one repetition maximum squat test? - Konstantin Warneke; Michael Keiner; David G. Behm; Klaus Wirth; Martin Kaufmann; Mareike Sproll; Andreas Konrad; Sebastian Wallot; Martin Hillebrecht (European Journal of Applied Physiology, 2024)
When measuring maximum strength, a high accuracy and precision is required to monitor the training adaptations. Based on available reliability parameters, the literature suggests the replacement of the one repetition maximum (1RM) by isometric testing to save testing time. However, from a statistical point of view, correlation coefficients do not provide the required information when aiming to replace one test by another. Therefore, the literature suggests the inclusion of the mean absolute error (MAE), the mean absolute percentage error (MAPE) for agreement analysis. Consequently, to check the replaceability of 1RM testing methods, the current study examined the agreement of isometric and dynamic testing methods in the squat and the isometric mid-thigh pull. While in accordance with the literature, correlations were classified high r = 0.638–0.828 and ICC = 0.630–0.828, the agreement analysis provided MAEs of 175.75–444.17 N and MAPEs of 16.16–57.71% indicating an intolerable high measurement error between isometric and dynamic testing conditions in the squat and isometric mid-thigh pull. In contrast to previous studies, using MAE, MAPE supplemented by CCC and BA analysis highlights the poor agreement between the included strength tests. The recommendation to replace 1RM testing with isometric testing routines in the squat does not provide suitable concordance and is not recommended.

Soil type and temperature determine soil respiration seasonal dynamics in dairy grassland - Yulin Liu; Jingjing Zhang; Martin Karl-Friedrich Bader; Sebastian Leuzinger (Soil Ecology Letters, 2024)
Soil respiration rates ( R s ) were measured in New Zealand dairy grassland. Both season and soil type significantly affected R s . Soil temperature and soil type dominated overall R s . Soil respiration ( R s ), the CO 2 release from root respiration and microbial metabolism, affects global soil carbon storage and cycling. Only few studies have looked at R s in the southern hemisphere, especially regarding the interaction between soil type and environmental factors on R s in dairy grassland. We investigated the relationship between R s and soil temperature ( T s ), soil water content (SWC), soil type, and other environmental factors based on summer and winter measurements at four sites in New Zealand. Across sites, soil respiration rates ranged from 0.29 to 14.58 with a mean of 5.38 ± 0.13 (mean ± standard error) µmol CO 2 m −2 s −1 . Mean summer R s was 86.5% higher than mean winter R s , largely driven by organic/gley and pumice soils while ultic soils showed very little seasonal temperature sensitivity. Overall mean R s in organic/gley soils was 108.0% higher than that in ultic soils. The high R s rate observed in organic/gley was likely due to high soil organic matter content, while low R s in ultic and pallic soils resulted from high clay content and low hydraulic conductance. Soil temperature drove overall R s . Our findings indicate that soil type and soil temperature together best explain R s . This implies that a mere classification of land use type may be insufficient for global C models and should be supplemented with soil type information, at least locally.

Generation, characterization, and toxicological assessment of reference ultrafine soot particles with different organic content for inhalation toxicological studies - Anusmita Das; Jana Pantzke; Seongho Jeong; Elena Hartner; Elias J. Zimmermann; Nadine Gawlitta; Svenja Offer; Deeksha Shukla; Anja Huber; Narges Rastak; Arūnas Meščeriakovas; Natalia P. Ivleva; et al. (Science of The Total Environment, 2024)

Groundwater-Surface water interactions research: Past trends and future directions - Dylan J. Irvine; Kamini Singha; Barret L. Kurylyk; Martin A. Briggs; Yakub Sebastian; Douglas R. Tait; Ashley M. Helton (Journal of Hydrology, 2024)

Serious gaming as potential training tool for recognition of adverse drug reactions: side-effect exposure—medical education (SeeMe) - Ingmar Bergs; Laura Bell; Sebastian Fedrowitz; Tim Krüger; Martin Lemos; Julia C. Stingl; Katja S. Just (European Journal of Clinical Pharmacology, 2024)
Purpose The recognition of adverse drug reactions (ADRs) is an important part of daily clinical work. However, medical education in this field is mostly drug-based and does not address adequately the complexity of this field regarding individual risk factors and polypharmacy. This study investigates the potential of the web-based serious game SeeMe (side-effect exposure—medical education) in pharmacological education of medical students to improve the recognition of relevant ADRs. Methods One hundred fifty-seven medical students were recruited to evaluate the serious game SeeMe . SeeMe was developed to improve knowledge and recognition of ADRs in clinical practice. Players take on the role of a physician trying to understand fictional patients with ADRs. Before and after an 8-week playing period, an evaluation was carried out through a pre- and post-questionnaire and a pre- and post- knowledge test. Results The students achieved significantly better results in the knowledge test, as almost twice as many exam-relevant questions were answered correctly ( p < 0.001). The serious game had a positive effect on the students’ perception of the importance of ADRs. Conclusion This study demonstrates the potential of web- and case-based fictional serious games in medical education. The improved recognition of side effects represents a crucial step for education and training in clinical pharmacology. Future versions of the serious game may take this further and focus on training in the treatment of ADRs and their relevance in various healthcare professions.

Assessing the potential for gas supersaturation downstream of hydropower plants in Norway, Austria and Germany - Ulrich Pulg; Robert J. Lennox; Martin Enqvist; Sebastian Franz Stranzl; Espen Olsen Espedal; Michael Schwarz; Andreas Lorke; Peter Flödl; Christoph Hauer; Martin Schletterer; Jo Halvard Halleraker; Gaute Velle (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Crop stress detection from UAVs: best practices and lessons learned for exploiting sensor synergies - Erekle Chakhvashvili; Miriam Machwitz; Michal Antala; Offer Rozenstein; Egor Prikaziuk; Martin Schlerf; Paul Naethe; Quanxing Wan; Jan Komárek; Tomáš Klouek; Sebastian Wieneke; Bastian Siegmann; et al. (Precision Agriculture, 2024)
Introduction Detecting and monitoring crop stress is crucial for ensuring sufficient and sustainable crop production. Recent advancements in unoccupied aerial vehicle (UAV) technology provide a promising approach to map key crop traits indicative of stress. While using single optical sensors mounted on UAVs could be sufficient to monitor crop status in a general sense, implementing multiple sensors that cover various spectral optical domains allow for a more precise characterization of the interactions between crops and biotic or abiotic stressors. Given the novelty of synergistic sensor technology for crop stress detection, standardized procedures outlining their optimal use are currently lacking. Materials and methods This study explores the key aspects of acquiring high-quality multi-sensor data, including the importance of mission planning, sensor characteristics, and ancillary data. It also details essential data pre-processing steps like atmospheric correction and highlights best practices for data fusion and quality control. Results Successful multi-sensor data acquisition depends on optimal timing, appropriate sensor calibration, and the use of ancillary data such as ground control points and weather station information. When fusing different sensor data it should be conducted at the level of physical units, with quality flags used to exclude unstable or biased measurements. The paper highlights the importance of using checklists, considering illumination conditions and conducting test flights for the detection of potential pitfalls. Conclusion Multi-sensor campaigns require careful planning not to jeopardise the success of the campaigns. This paper provides practical information on how to combine different UAV-mounted optical sensors and discuss the proven scientific practices for image data acquisition and post-processing in the context of crop stress monitoring.

Ticks infesting terrestrial small mammals in a rural settlement in the Amazonas state, Brazil - Juliana Machado Portela; Alessandra Ferreira Dales Nava; Helder Ribeiro Batista; Thiago F. Martins; Sebastian Muñoz-Leal; Maria Nazareth Ferreira da Silva; Salatiel Ribeiro Dias; Marcelo B. Labruna; Antonio Humberto Hamad Minervino (Experimental and Applied Acarology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

A multi-sensor approach to measuring hydrodynamic parameters in a pyrite-quartz flotation system - Hifsa Pervez; Ali Hassan; Anna-Elisabeth Sommer; Till Zürner; Lucas Pereira; Martin Rudolph; Sebastian Maaß; Jesse Bowden; Kerstin Eckert (Minerals Engineering, 2024)

Museomics help resolving the phylogeny of snowfinches (Aves, Passeridae, Montifringilla and allies) - Safiqul Islam; Claire Peart; Christian Kehlmaier; Yue-Hua Sun; Fumin Lei; Andreas Dahl; Sylvia Klemroth; Dimitra Alexopoulou; Maria del Mar Delgado; Paola Laiolo; Juan Carlos Illera; Sebastian Dirren; et al. (Molecular Phylogenetics and Evolution, 2024)

Core–Shell catalyst particles for tandem catalysis: An experimental/numerical approach towards optimal design - Najmeh Bashiri; Georg Brösigke; Esteban Gioria; Johannes Schmidt; Martin Konrad; Rafael L. Oliveira; Michael Geske; Frank Rosowski; Sebastian Matera; Reinhard Schomäcker; Arne Thomas; Jens-Uwe Repke (Chemical Engineering Journal, 2024)

Understanding land take by low-density residential areas: An institutionalist perspective on local planning authorities, developers and households - Sebastian Eichhorn; Denise Ehrhardt; Angelika Münter; Martin Behnisch; Mathias Jehling (Land Use Policy, 2024)

Postglacial evolution of the Lake Constance shelf and its relation to a 10-km long chain of submerged Neolithic mounds - Dominic Perler; Simone Benguerel; Hansjörg Brem; Florence Gilliard; Jens Hornung; Thomas Keiser; Urs Leuzinger; Sebastian Schaller; Sönke Szidat; Hendrik Vogel; Martin Wessels; Flavio S. Anselmetti (Journal of Paleolimnology, 2024)
A recent bathymetric survey of Lake Constance revealed ~ 170 mounds composed of loosely deposited rocks aligned in a ~ 10-km long chain along the southern Swiss shoreline in a water depth of 3–5 m. The mounds are 10–30 m in diameter and up to 1.5 m high. Over their entire length of occurrence, the mounds are estimated to be composed of ~ 60 million individual boulders, with a total weight of ~ 78,000 t. A ground penetrating radar (GPR) survey showed that the mounds are not linked to the glacial substrate but were rather deposited artificially on the edge of a prograding shelf composed of Holocene lake sediments. Here, we present the results of a coring campaign with four piston cores along a GPR transect across one of the mounds. The cores recovered the full Holocene sedimentary succession all the way into the basal till that is overlain by lacustrine sediments dating back to ~ 14,400 cal. yrs BP. The four cores are merged into a ~ 12.4-m long composite section reflecting continuous sedimentation from the siliciclastic-dominated Late Glacial to the carbonate-rich Late Holocene. The stratigraphic horizon representing the mound’s construction was radiocarbon-dated to ~ 5600–5300 cal. yrs BP, placing them in the Neolithic period. This age was confirmed by radiocarbon dating of wood samples collected during underwater excavation of the mounds. Geochemical analysis of the Holocene sedimentary succession shows generally high carbonate contents (average of 69%). The interval from 5750 to 4950 cal. yrs BP, a part of the mound period, is characterized by a Holocene minimum in carbonate content (average of 57%) and by larger mean grain sizes. Comparing these values to those from a recent surface-sediment depth transect indicates that this was a period of rather low lake levels, which might have favoured mound construction. Correlations to nearby archaeological sites and to the general West-Central European lake-level record indicates that the mounds likely were built during a short phase of low lake levels during a general trend of climatic cooling followed by a lake-level transgression.

The excitability of ipsilateral motor evoked potentials is not task-specific and spatially distinct from the contralateral motor hotspot - Nelly Seusing; Sebastian Strauss; Robert Fleischmann; Christina Nafz; Sergiu Groppa; Muthuraman Muthuraman; Hao Ding; Winston D. Byblow; Martin Lotze; Matthias Grothe (Experimental Brain Research, 2024)
Objective The role of ipsilateral descending motor pathways in voluntary movement of humans is still a matter of debate, with partly contradictory results. The aim of our study therefore was to examine the excitability of ipsilateral motor evoked potentials (iMEPs) regarding site and the specificity for unilateral and bilateral elbow flexion extension tasks. Methods MR-navigated transcranial magnetic stimulation mapping of the dominant hemisphere was performed in twenty healthy participants during tonic unilateral (iBB), bilateral homologous (bBB) or bilateral antagonistic elbow flexion-extension (iBB-cAE), the map center of gravity (CoG) and iMEP area from BB were obtained. Results The map CoG of the ipsilateral BB was located more anterior-laterally than the hotspot of the contralateral BB within the primary motor cortex, with a significant difference in CoG in iBB and iBB-cAE, but not bBB compared to the hotspot for the contralateral BB (each p < 0.05). However, different tasks had no effect on the size of the iMEPs. Conclusion Our data demonstrated that excitability of ipsilateral and contralateral MEP differ spatially in a task-specific manner suggesting the involvement of different motor networks within the motor cortex.

Exploring Paleogene Tibet's warm temperate environments through target enrichment and phylogenetic niche modelling of Himalayan spiny frogs (Paini, Dicroglossidae) - Sylvia Hofmann; Dennis Rödder; Tobias Andermann; Michael Matschiner; Jendrian Riedel; Chitra B. Baniya; Morris Flecks; Jianhuan Yang; Ke Jiang; Jiang Jianping; Spartak N. Litvinchuk; Sebastian Martin; et al. (Molecular Ecology, 2024)
The Cenozoic topographic development of the Himalaya‐Tibet orogen (HTO) substantially affected the paleoenvironment and biodiversity patterns of High Asia. However, concepts on the evolution and paleoenvironmental history of the HTO differ massively in timing, elevational increase and sequence of surface uplift of the different elements of the orogen. Using target enrichment of a large set of transcriptome‐derived markers, ancestral range estimation and paleoclimatic niche modelling, we assess a recently proposed concept of a warm temperate paleo‐Tibet in Asian spiny frogs of the tribe Paini and reconstruct their historical biogeography. That concept was previously developed in invertebrates. Because of their early evolutionary origin, low dispersal capacity, high degree of local endemism, and strict dependence on temperature and humidity, the cladogenesis of spiny frogs may echo the evolution of the HTO paleoenvironment. We show that diversification of main lineages occurred during the early to Mid‐Miocene, while the evolution of alpine taxa started during the late Miocene/early Pliocene. Our distribution and niche modelling results indicate range shifts and niche stability that may explain the modern disjunct distributions of spiny frogs. They probably maintained their (sub)tropical or (warm)temperate preferences and moved out of the ancestral paleo‐Tibetan area into the Himalaya as the climate shifted, as opposed to adapting in situ. Based on ancestral range estimation, we assume the existence of low‐elevation, climatically suitable corridors across paleo‐Tibet during the Miocene along the Kunlun, Qiangtang and/or Gangdese Shan. Our results contribute to a deeper understanding of the mechanisms and processes of faunal evolution in the HTO.

Trophic effects of Bti-based mosquito control on two top predators in floodplain pond mesocosms - Verena Gerstle; Eric Bollinger; Alessandro Manfrin; Sebastian Pietz; Sara Kolbenschlag; Alexander Feckler; Martin H. Entling; Carsten A. Brühl (Environmental Science and Pollution Research, 2024)
Chironomid (Diptera: Chironomidae) larvae play a key role in aquatic food webs as prey for predators like amphibian and dragonfly larvae. This trophic link may be disrupted by anthropogenic stressors such as Bacillus thuringiensis var . israelensis (Bti), a biocide widely used in mosquito control. In a companion study, we recorded a 41% reduction of non-target larval chironomids abundance in outdoor floodplain pond mesocosms (FPMs) treated with Bti. Therefore, we examined the diet of two top predators in the FPMs, larvae of the palmate newt (Salamandridae: Lissotriton helveticus ) and dragonfly (Aeshnidae: predominantly Anax imperator ), using bulk stable isotope analyses of carbon and nitrogen. Additionally, we determined neutral lipid fatty acids in newt larvae to assess diet-related effects on their physiological condition. We did not find any effects of Bti on the diet proportions of newt larvae and no significant effects on the fatty acid content. We observed a trend in Aeshnidae larvae from Bti-FPMs consuming a higher proportion of large prey (Aeshnidae, newt, damselfly larvae; ~42%), and similar parts of smaller prey (chironomid, mayfly, Libellulidae, and zooplankton), compared to controls. Our findings may suggest bottom-up effects of Bti on aquatic predators but should be further evaluated, for instance, by using compound-specific stable isotope analyses of fatty acids or metabarcoding approaches.

Assessing landscape-level effects of permanent grassland management and landscape configuration on open-land butterflies based on national monitoring data - Toni Kasiske; Jens Dauber; Petra Dieker; Alexander Harpke; Sebastian Klimek; Elisabeth Kühn; Christian Levers; Marcel Schwieder; Josef Settele; Martin Musche (Biodiversity and Conservation, 2024)
Halting and reversing the ongoing insect decline requires in-depth knowledge on key drivers. Due to their sensitivity to habitat quality, butterflies are valuable indicators for grassland management intensity, including mowing. However, most studies examining mowing regime impacts on butterflies are limited to small spatial extents. Here, we tested the potential of citizen science butterfly monitoring data for assessing landscape-level effects of mowing regimes (number of mowing events and timing of the first event) and edge density (density of boundaries between different land-cover types) on butterfly richness, abundance, and community composition. We used generalised linear mixed-effects models to relate nationwide data from the German Butterfly Monitoring Scheme (DEBMS) to high-resolution satellite imagery on mowing events in permanent grasslands (grasslands excluded from crop rotation). As butterfly transects may not consistently be located within grasslands, we ran our models for different thresholds from 0 to 50%, representing increasing shares of the transect route situated within permanent grasslands (10% intervals). We did not find significant associations between mowing regimes and butterflies when focussing on species richness and abundance of all species inhabiting open land. However, we found strong positive associations of delayed mowing with the abundance of grassland specialists with increasing grassland shares per transect. Further, we found negative associations of delayed mowing with the annual number of generations and of more frequent mowing with the abundance of specialists, depending on the share of grassland per transect. Edge density had a positive association with species richness and abundance of species inhabiting open land, as well as abundance of grassland indicator species and grassland specialists in landscapes with a low grassland share per transect. Our findings underscore the importance of low-intensity managed permanent grasslands at the landscape scale for specialised butterflies. Additionally, we highlight the importance of a high density of boundaries for open-land and specialised butterflies, particularly in landscapes with highly fragmented permanent grasslands. To improve future analyses of grassland management impacts, we recommend expanding DEBMS monitoring sites to cover a larger grassland management intensity gradient and to place more transects within grasslands.

Non-crossing Quantile Regression Neural Network as a Calibration Tool for Ensemble Weather Forecasts - Mengmeng Song; Dazhi Yang; Sebastian Lerch; Xiang’ao Xia; Gokhan Mert Yagli; Jamie M. Bright; Yanbo Shen; Bai Liu; Xingli Liu; Martin János Mayer (Advances in Atmospheric Sciences, 2024)

Impact of natural organic matter and inorganic ions on the stabilization of polystyrene micro-particles - Lars Eitzen; Aki Sebastian Ruhl; Martin Jekel (Science of The Total Environment, 2024)

The global distribution of Isoprenoidal Glycerol Dialkyl Diethers (isoGDDs) is consistent with a predominant degradation origin - Joe S. Hingley; César C. Martins; Chloe Walker-Trivett; Jennifer K. Adams; Sebastian Naeher; Christoph Häggi; Sarah J. Feakins; B.D.A. Naafs (Organic Geochemistry, 2024)

In vitro susceptibility of Neisseria gonorrhoeae to netilmicin and etimicin in comparison to gentamicin and other aminoglycosides - Sonja Gross; Sebastian Herren; Marina Gysin; Anna Rominski; Anna Roditscheff; Martin Risch; Frank Imkamp; David Crich; Sven N. Hobbie (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose Single doses of gentamicin have demonstrated clinical efficacy in the treatment of urogenital gonorrhea, but lower cure rates for oropharyngeal and anorectal gonorrhea. Formulations selectively enriched in specific gentamicin C congeners have been proposed as a less toxic alternative to gentamicin, potentially permitting higher dosing to result in increased plasma exposures at the extragenital sites of infection. The purpose of the present study was to compare the antibacterial activity of individual gentamicin C congeners against Neisseria gonorrhoeae to that of other aminoglycoside antibiotics. Methods Antimicrobial susceptibility of three N. gonorrhoeae reference strains and 152 clinical isolates was assessed using standard disk diffusion, agar dilution, and epsilometer tests. Results Gentamicin C1, C2, C1a, and C2a demonstrated similar activity against N. gonorrhoeae . Interestingly, susceptibility to the 1- N -ethylated aminoglycosides etimicin and netilmicin was significantly higher than the susceptibility to their parent compounds gentamicin C1a and sisomicin, and to any other of the 25 aminoglycosides assessed in this study. Propylamycin, a 4’-propylated paromomycin analogue, was significantly more active against N. gonorrhoeae than its parent compound, too. Conclusion Selectively enriched gentamicin formulations hold promise for a less toxic but equally efficacious alternative to gentamicin. Our study warrants additional consideration of the clinically established netilmicin and etimicin for treatment of genital and perhaps extragenital gonorrhea. Additional studies are required to elucidate the mechanism behind the advantage of alkylated aminoglycosides.

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

A multi-scenario risk assessment strategy applied to mixtures of chemicals of emerging concern in the River Aconcagua basin in Central Chile - Pedro A. Inostroza; Sebastian Elgueta; Martin Krauss; Werner Brack; Thomas Backhaus (Science of The Total Environment, 2024)

The FluidFlower Validation Benchmark Study for the Storage of CO$$_2$$ - Bernd Flemisch; Jan M. Nordbotten; Martin Fernø; Ruben Juanes; Jakub W. Both; Holger Class; Mojdeh Delshad; Florian Doster; Jonathan Ennis-King; Jacques Franc; Sebastian Geiger; Dennis Gläser; et al. (Transport in Porous Media, 2024)
Successful deployment of geological carbon storage (GCS) requires an extensive use of reservoir simulators for screening, ranking and optimization of storage sites. However, the time scales of GCS are such that no sufficient long-term data is available yet to validate the simulators against. As a consequence, there is currently no solid basis for assessing the quality with which the dynamics of large-scale GCS operations can be forecasted. To meet this knowledge gap, we have conducted a major GCS validation benchmark study. To achieve reasonable time scales, a laboratory-size geological storage formation was constructed (the “FluidFlower”), forming the basis for both the experimental and computational work. A validation experiment consisting of repeated GCS operations was conducted in the FluidFlower, providing what we define as the true physical dynamics for this system. Nine different research groups from around the world provided forecasts, both individually and collaboratively, based on a detailed physical and petrophysical characterization of the FluidFlower sands. The major contribution of this paper is a report and discussion of the results of the validation benchmark study, complemented by a description of the benchmarking process and the participating computational models. The forecasts from the participating groups are compared to each other and to the experimental data by means of various indicative qualitative and quantitative measures. By this, we provide a detailed assessment of the capabilities of reservoir simulators and their users to capture both the injection and post-injection dynamics of the GCS operations.

The multiple sulfur isotope architecture of the Kambalda nickel camp, Western Australia - Sebastian Staude; Laure A.J. Martin; Matvei Aleshin; Marco L. Fiorentini; Gregor Markl (Mineralium Deposita, 2024)
New data on the multiple sulfur isotope signature of Archean sulfides from country rocks and magmatic mineralization at the Moran deposit (Kambalda, Western Australia) were combined with previously published geochemical data to constrain the various stages of the dynamic evolution of this magmatic system, unveiling new insights into the transport mechanisms of sulfide liquids in komatiite magmas. Sulfides in the Archean magmatic and sedimentary host rocks of the komatiites display a unique mass-independent sulfur isotope signature (Δ 33 S), which records a photochemical reaction of sulfur in an oxygen-poor atmosphere prior to the Great Oxidation Event. Sedimentary rocks that are thought to be assimilated by komatiite show a distinctly positive Δ 33 S signature (+ 0.9 to + 2.4‰). Early ore sulfides situated above these sedimentary rocks contain relatively few valuable metals and display an overlapping Δ 33 S range (+ 0.6 to + 1.0‰). Subsequent but still early ore sulfides are situated above basalt, as the sedimentary rocks were thermo-mechanically eroded by the sulfide melt, displaying more mantle-like signatures (+ 0.2 to + 0.3‰) and valuable metal content - indistinguishable from the main ore deposit. This reflects a progressive dilution of the contaminant signature by the magmatic isotope signature of the komatiite liquid. Calculated volumes of the interaction of silicate melt and sulfide melt to explain the metal tenor of the ore and its Δ 33 S signature indicate a decoupling between chemical and isotopic signatures. This can be explained by upgrading the sulfide melt with valuable metals simultaneously with the dissolution of sulfur in the komatiite melt.

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Discrepant mass accumulation rates of sediments in the South Pacific Ocean from 230Th and 3He measurements - Frank J. Pavia; Jordan T. Abell; Jennifer L. Middleton; Annie Leal; Sebastian M. Vivancos; Martin Q. Fleisher; Gisela Winckler; Robert F. Anderson (Geochimica et Cosmochimica Acta, 2024)

Essential omega‐3 fatty acids are depleted in sea ice and pelagic algae of the Central Arctic Ocean - Katrin Schmidt; Martin Graeve; Clara J. M. Hoppe; Sinhué Torres‐Valdes; Nahid Welteke; Laura M. Whitmore; Philipp Anhaus; Angus Atkinson; Simon T. Belt; Tina Brenneis; Robert G. Campbell; Giulia Castellani; et al. (Global Change Biology, 2024)
Microalgae are the main source of the omega‐3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), essential for the healthy development of most marine and terrestrial fauna including humans. Inverse correlations of algal EPA and DHA proportions (% of total fatty acids) with temperature have led to suggestions of a warming‐induced decline in the global production of these biomolecules and an enhanced importance of high latitude organisms for their provision. The cold Arctic Ocean is a potential hotspot of EPA and DHA production, but consequences of global warming are unknown. Here, we combine a full‐seasonal EPA and DHA dataset from the Central Arctic Ocean (CAO), with results from 13 previous field studies and 32 cultured algal strains to examine five potential climate change effects; ice algae loss, community shifts, increase in light, nutrients, and temperature. The algal EPA and DHA proportions were lower in the ice‐covered CAO than in warmer peripheral shelf seas, which indicates that the paradigm of an inverse correlation of EPA and DHA proportions with temperature may not hold in the Arctic. We found no systematic differences in the summed EPA and DHA proportions of sea ice versus pelagic algae, and in diatoms versus non‐diatoms. Overall, the algal EPA and DHA proportions varied up to four‐fold seasonally and 10‐fold regionally, pointing to strong light and nutrient limitations in the CAO. Where these limitations ease in a warming Arctic, EPA and DHA proportions are likely to increase alongside increasing primary production, with nutritional benefits for a non‐ice‐associated food web.

Resources and tools for studying convergent evolution in different lineages of smut fungi - Lena Steins; Marine Duhamel; Sebastian Klenner-Koch; Dominik Begerow; Martin Kemler (Mycological Progress, 2023)
Convergent evolution is the phenomenon of similar traits evolving independently in different lineages of the tree of life. Studying convergent evolution provides an excellent opportunity to understand natural selection for specific traits and physiological constraints to evolution that allow a broadened view on evolutionary mechanisms as a whole. Smut fungi, a polyphyletic group of plant-parasitic fungi with a specific infection and life cycle pattern, are a prime example of convergent evolution. Most notably, smut fungi in the genus Microbotryum that belongs to the subdivision Pucciniomycotina and smut fungi from the subdivision Ustilaginomycotina show strong similarities despite millions of years of independent evolution. However, the conceptual connections drawn between the two groups are scarce, thereby limiting the opportunities for exploring convergent evolution between these taxa. To facilitate knowledge exchange within the research community, we provide a summary of databases, molecular and biological tools and a brief introduction to the structure of populations and the characteristics of host specificity in both groups. Furthermore, we compare the life cycles and research emphases between the two groups. The comparisons are supplemented with an analysis of genome composition and gene function, which aims to advance research on the convergent evolution of smut fungi using existing data.

Yield of lucerne-grass mixtures did not differ from lucerne pure stands in a multi-site field experiment - Sebastian Christoph Glowacki; Martin Komainda; Edmund Leisen; Johannes Isselstein (European Journal of Agronomy, 2023)

A red listing gap analysis of molluscs and crustaceans in Northern Europe: What has happened in the last 10 years? - Sarah J. Bourlat; Georg F. Tschan; Sebastian Martin; Muhammad Iqram; Sonja Leidenberger (Biological Conservation, 2023)

What do older patients know about their medication? A cross-sectional, interview-based pilot study - Olaf Krause; Corinna T. Ziemann; Martin Schulze Westhoff; Sebastian Schröder; Benjamin Krichevsky; Stephan Greten; Dirk O. Stichtenoth; Johannes Heck (European Journal of Clinical Pharmacology, 2023)
Purpose This study sought to analyze the medication knowledge and awareness of medication adjustment options during intercurrent illness (sick day rules) of patients ≥ 70 years treated at a hospital for geriatric medicine in northern Germany. Methods The study was designed as a cross-sectional, interview-based pilot study, was approved by the Ethics Committee of Hannover Medical School (No. 10274_BO_K_2022; date of approval: 11 March 2022), and enrolled a convenience sample of 100 patients between May and December 2022. Results The median of the average medication knowledge score in the study population (median age 82 years (IQR 75–87); 71% female) was 5 on a scale from 0 to 6 (IQR 3.8–5.6). Women achieved higher average medication knowledge scores than men (median 5.1 (IQR 4–5.6) vs. median 4.3 (IQR 3.6–5.1); p = 0.012), and patients < 80 years achieved higher average medication knowledge scores than patients ≥ 80 years (median 5.4 (IQR 4.9–5.7) vs. median 4.3 (IQR 3.2–5.3); p < 0.001). Sick day rules were known for only 1.1% of drugs for which sick day rules were applicable. Fifty-two percent of the patients reported that their general practitioner contributed most to their medication knowledge, and 66% considered their daily number of drugs to take adequate. Conclusion Our study showed that medication knowledge of older patients was overall satisfying. Awareness of sick day rules, however, was poor. Future studies should evaluate the clinical benefits of sick day rules and ways of better communicating sick day rules to patients. In this regard, general practitioners may play a decisive role.

Consistent benefits of fungicide reduction on arthropod predators and predation rates in viticulture: a five-year experiment - Jo Marie Reiff; Theresa Pennington; Sebastian Kolb; Konrad Theiss; Ekaterina Alakina; Marvin Ehringer; Paul Mason; Rosalie Shrestha; Martin H. Entling; Christoph Hoffmann (BioControl, 2023)
For reliable pest suppression, benefits of habitat management for natural enemies of agricultural pests need to be consistent over time. Unfortunately, most research projects allow only for one or two years of data collection. Here, we present a five-year study on effects of fungicide reduction and altered plant architecture on arthropod abundances and natural pest control in an experimental vineyard. The vineyard rows were divided into eight groups, half of which were trained in vertical shoot position (“trellis system”) and the other half as semi-minimal pruned hedge (“minimal pruning”). Every row was divided in three sections receiving three different plant protection intensities, respectively, with fungicides certified for organic viticulture. In each year we sampled arthropods from the grapevine canopy by standardized leaf collection and beat-sheet sampling, and exposed baits of a major grapevine pest ( Lobesia botrana ) to assess natural pest control. Arthropods, in particular predators, benefited from reduced fungicide sprayings and in turn promoted natural pest control. In contrast, effects of minimal pruning were less strong, and restricted to the leaf mesofauna, earwigs and leafhoppers. Across the five study years with their variable weather conditions, we conclude that the advantages of reduced fungicide sprayings in fungus-resistant varieties are consistent over time.

Histopathological screening of Pontogammarus robustoides (Amphipoda), an invader on route to the United Kingdom - Daniel A. Warren; Amy L. Burgess; Sebastian Prati; Karolina Bacela-Spychalska; Martin S. J. Rogers; Jamie Bojko (Journal of Invertebrate Pathology, 2023)

Association of blood cadmium and lead levels with self-reported reproductive lifespan and pregnancy loss: The national health and nutrition examination survey 1999–2018 - Roberto Gonzalez-Martin; Maria Grau-Perez; Patricia Sebastian-Leon; Patricia Diaz-Gimeno; Carmen Vidal; Maria Tellez-Plaza; Francisco Dominguez (Environmental Research, 2023)

Polycyclic aromatic hydrocarbons including dibenzopyrenes in indoor air samples from schools and residences in Germany - Hermann Fromme; Marina Sysoltseva; Christine Achten; Talisa Bühl; Claudia Röhl; Sebastian Leubner; Felicia Gerull; Andreas Gessner; Martin Kraft; Rafael Burghardt; Wolfgang Schober; Wolfgang Völkel (Atmospheric Environment, 2023)

Pilot-scale removal of persistent and mobile organic substances in granular activated carbon filters and experimental predictability at lab-scale - Pia Schumann; Dario Müller; Paulina Eckardt; Matthias Muschket; Daniel Dittmann; Luisa Rabe; Kristin Kerst; André Lerch; Thorsten Reemtsma; Martin Jekel; Aki Sebastian Ruhl (Science of The Total Environment, 2023)

The EnMAP imaging spectroscopy mission towards operations - Tobias Storch; Hans-Peter Honold; Sabine Chabrillat; Martin Habermeyer; Paul Tucker; Maximilian Brell; Andreas Ohndorf; Katrin Wirth; Matthias Betz; Michael Kuchler; Helmut Mühle; Emiliano Carmona; et al. (Remote Sensing of Environment, 2023)

Interstitial carbonates in pillowed metabasaltic rocks from the Pilbara Craton, Western Australia: A vestige of Archean seawater chemistry and seawater-rock interactions - Chris S. Marien; Oliver Jäger; Jonas Tusch; Sebastian Viehmann; Jakub Surma; Martin J. Van Kranendonk; Carsten Münker (Precambrian Research, 2023)

Regional variation in deadwood decay of 13 tree species: Effects of climate, soil and forest structure - Pascal Edelmann; Wolfgang W. Weisser; Didem Ambarlı; Claus Bässler; François Buscot; Martin Hofrichter; Björn Hoppe; Harald Kellner; Cynthia Minnich; Julia Moll; Derek Persoh; Sebastian Seibold; et al. (Forest Ecology and Management, 2023)

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Biodiversity conservation, ecosystem services and organic viticulture: A glass half-full - Léa Beaumelle; Brice Giffard; Pauline Tolle; Silvia Winter; Martin H. Entling; Emilio Benítez; Johann G. Zaller; Arthur Auriol; Olivier Bonnard; Yohan Charbonnier; Olivier Fabreguettes; Benjamin Joubard; et al. (Agriculture, Ecosystems & Environment, 2023)

Ambient and substrate energy influence decomposer diversity differentially across trophic levels - Peter Kriegel; Sebastian Vogel; Romain Angeleri; Petr Baldrian; Werner Borken; Christophe Bouget; Antoine Brin; Heinz Bussler; Cristiana Cocciufa; Benedikt Feldmann; Martin M. Gossner; Elena Haeler; et al. (Ecology Letters, 2023)
The species‐energy hypothesis predicts increasing biodiversity with increasing energy in ecosystems. Proxies for energy availability are often grouped into ambient energy (i.e., solar radiation) and substrate energy (i.e., non‐structural carbohydrates or nutritional content). The relative importance of substrate energy is thought to decrease with increasing trophic level from primary consumers to predators, with reciprocal effects of ambient energy. Yet, empirical tests are lacking. We compiled data on 332,557 deadwood‐inhabiting beetles of 901 species reared from wood of 49 tree species across Europe. Using host‐phylogeny‐controlled models, we show that the relative importance of substrate energy versus ambient energy decreases with increasing trophic levels: the diversity of zoophagous and mycetophagous beetles was determined by ambient energy, while non‐structural carbohydrate content in woody tissues determined that of xylophagous beetles. Our study thus overall supports the species‐energy hypothesis and specifies that the relative importance of ambient temperature increases with increasing trophic level with opposite effects for substrate energy.

Covalent polyphenol modification of a reactive cysteine in the major apple allergen Mal d 1 - Jana Unterhauser; Linda Ahammer; Tobias Rainer; Reiner Eidelpes; Sebastian Führer; Bettina Nothegger; Claudia E. Covaciu; Valentina Cova; Anna S. Kamenik; Klaus R. Liedl; Thomas Müller; Kathrin Breuker; et al. (Food Chemistry, 2023)

Smaller human populations are still not a necessary condition for biodiversity conservation: A response to Cafaro et al. (2023) - Alice C. Hughes; Kévin Tougeron; Dominic A. Martin; Filippo Menga; Bruno H.P. Rosado; Sebastian Villasante; Shweta Madgulkar; Fernando Gonçalves; Luisa Maria Diele-Viegas; Sheila R. Colla; Vitor de Andrade Kamimura; Holly Caggiano; et al. (Biological Conservation, 2023)

Warmer winters result in reshaping of the European beech forest soil microbiome (bacteria, archaea and fungi)—With potential implications for ecosystem functioning - Mathilde Borg Dahl; Juergen Kreyling; Sebastian Petters; Haitao Wang; Martin Steen Mortensen; Lorrie Maccario; Søren J. Sørensen; Tim Urich; Robert Weigel (Environmental Microbiology, 2023)
In temperate regions, climate warming alters temperature and precipitation regimes. During winter, a decline in insulating snow cover changes the soil environment, where especially frost exposure can have severe implications for soil microorganisms and subsequently for soil nutrient dynamics. Here, we investigated winter climate change responses in European beech forests soil microbiome. Nine study sites with each three treatments (snow exclusion, insolation, and ambient) were investigated. Long‐term adaptation to average climate was explored by comparing across sites. Triplicated treatment plots were used to evaluate short‐term (one single winter) responses. Community profiles of bacteria, archaea and fungi were created using amplicon sequencing. Correlations between the microbiome, vegetation and soil physicochemical properties were found. We identify core members of the forest‐microbiome and link them to key processes, for example, mycorrhizal symbiont and specialized beech wood degraders (fungi) and nitrogen cycling (bacteria, archaea). For bacteria, the shift of the microbiome composition due to short‐term soil temperature manipulations in winter was similar to the community differences observed between long‐term relatively cold to warm conditions. The results suggest a strong link between the changes in the microbiomes and changes in environmental processes, for example, nitrogen dynamics, driven by variations in winter climate.

Is adsorption onto activated carbon a feasible drinking water treatment option for persistent and mobile substances? - Pia Schumann; Matthias Muschket; Daniel Dittmann; Luisa Rabe; Thorsten Reemtsma; Martin Jekel; Aki Sebastian Ruhl (Water Research, 2023)

Contractile properties are less affected at long than short muscle length after eccentric exercise - Emeric Chalchat; Julien Siracusa; Cyprien Bourrilhon; Keyne Charlot; Jean-Luc Gennisson; Sebastian Garcia-Vicencio; Vincent Martin (European Journal of Applied Physiology, 2023)

Meta-omics profiling of full-scale groundwater rapid sand filters explains stratification of iron, ammonium and manganese removals - Francesc Corbera-Rubio; Michele Laureni; Nienke Koudijs; Simon Müller; Theo van Alen; Frank Schoonenberg; Sebastian Lücker; Martin Pabst; Mark C.M. van Loosdrecht; Doris van Halem (Water Research, 2023)

Farmer advisory systems and pesticide use in legume-based systems in West Africa - Martin Paul Jr. Tabe-Ojong; Yong Sebastian Nyam; Jourdain C. Lokossou; Bisrat Haile Gebrekidan (Science of The Total Environment, 2023)

A pioneer morphological and genetic study of the intertidal fauna of the Gerlache Strait (Antarctic Peninsula) - Quentin Jossart; David Bauman; Camille VE Moreau; Thomas Saucède; Henrik Christiansen; Madeleine J. Brasier; Peter Convey; Rachel Downey; Blanca Figuerola; Patrick Martin; Jon Norenburg; Sebastian Rosenfeld; et al. (Environmental Monitoring and Assessment, 2023)

When things get MESI: The Manipulation Experiments Synthesis Initiative—A coordinated effort to synthesize terrestrial global change experiments - Kevin Van Sundert; Sebastian Leuzinger; Martin K.‐F. Bader; Scott X. Chang; Martin G. De Kauwe; Jeffrey S. Dukes; J. Adam Langley; Zilong Ma; Bertold Mariën; Simon Reynaert; Jingyi Ru; Jian Song; et al. (Global Change Biology, 2023)
Responses of the terrestrial biosphere to rapidly changing environmental conditions are a major source of uncertainty in climate projections. In an effort to reduce this uncertainty, a wide range of global change experiments have been conducted that mimic future conditions in terrestrial ecosystems, manipulating CO 2 , temperature, and nutrient and water availability. Syntheses of results across experiments provide a more general sense of ecosystem responses to global change, and help to discern the influence of background conditions such as climate and vegetation type in determining global change responses. Several independent syntheses of published data have yielded distinct databases for specific objectives. Such parallel, uncoordinated initiatives carry the risk of producing redundant data collection efforts and have led to contrasting outcomes without clarifying the underlying reason for divergence. These problems could be avoided by creating a publicly available, updatable, curated database. Here, we report on a global effort to collect and curate 57,089 treatment responses across 3644 manipulation experiments at 1145 sites, simulating elevated CO 2 , warming, nutrient addition, and precipitation changes. In the resulting Manipulation Experiments Synthesis Initiative (MESI) database, effects of experimental global change drivers on carbon and nutrient cycles are included, as well as ancillary data such as background climate, vegetation type, treatment magnitude, duration, and, unique to our database, measured soil properties. Our analysis of the database indicates that most experiments are short term (one or few growing seasons), conducted in the USA, Europe, or China, and that the most abundantly reported variable is aboveground biomass. We provide the most comprehensive multifactor global change database to date, enabling the research community to tackle open research questions, vital to global policymaking. The MESI database, freely accessible at doi.org/10.5281/zenodo.7153253 , opens new avenues for model evaluation and synthesis‐based understanding of how global change affects terrestrial biomes. We welcome contributions to the database on GitHub.

Carbon farming: Are soil carbon certificates a suitable tool for climate change mitigation? - Carsten Paul; Bartosz Bartkowski; Cenk Dönmez; Axel Don; Stefanie Mayer; Markus Steffens; Sebastian Weigl; Martin Wiesmeier; André Wolf; Katharina Helming (Journal of Environmental Management, 2023)

The effect of relative humidity on eddy covariance latent heat flux measurements and its implication for partitioning into transpiration and evaporation - Weijie Zhang; Martin Jung; Mirco Migliavacca; Rafael Poyatos; Diego G. Miralles; Tarek S. El-Madany; Marta Galvagno; Arnaud Carrara; Nicola Arriga; Andreas Ibrom; Ivan Mammarella; Dario Papale; et al. (Agricultural and Forest Meteorology, 2023)

Cyanotoxins associated with macrophytes in Berlin (Germany) water bodies – Occurrence and risk assessment - Jutta Fastner; Jonna Teikari; Anja Hoffmann; Antje Köhler; Sebastian Hoppe; Elke Dittmann; Martin Welker (Science of The Total Environment, 2023)

Association between iron accumulation in the dorsal striatum and compulsive drinking in alcohol use disorder - Haoye Tan; Simon Hubertus; Sebastian Thomas; Alycia M. Lee; Sarah Gerhardt; Martin Fungisai Gerchen; Wolfgang H. Sommer; Falk Kiefer; Lothar Schad; Sabine Vollstädt-Klein (Psychopharmacology, 2023)
Rationale Brain iron accumulation has been observed in neuropsychiatric disorders and shown to be related to neurodegeneration. Objectives In this study, we used quantitative susceptibility mapping (QSM), an emerging MRI technique developed for quantifying tissue magnetic susceptibility, to examine brain iron accumulation in individuals with alcohol use disorder (AUD) and its relation to compulsive drinking. Methods Based on our previous projects, QSM was performed as a secondary analysis with gradient echo sequence images, in 186 individuals with AUD and 274 healthy participants. Whole-brain susceptibility values were calculated with morphology-enabled dipole inversion and referenced to the cerebrospinal fluid. Then, the susceptibility maps were compared between AUD individuals and healthy participants. The relationship between drinking patterns and susceptibility was explored. Results Whole-brain analyses showed that the susceptibility in the dorsal striatum (putamen and caudate) among AUD individuals was higher than healthy participants and was positively related to the Obsessive Compulsive Drinking Scale (OCDS) scores and the amount of drinking in the past three months. Conclusions Increased susceptibility suggests higher iron accumulation in the dorsal striatum in AUD. This surrogate for the brain iron level was linearly associated with the compulsive drinking pattern and the recent amount of drinking, which provides us a new clinical perspective in relation to brain iron accumulation, and also might indicate an association of AUD with neuroinflammation as a consequence of brain iron accumulation. The iron accumulation in the striatum is further relevant for functional imaging studies in AUD by potentially producing signal dropout and artefacts in fMRI images.

Using fluorescence lifetime imaging to disentangle microbes from the heterogeneous soil matrix - Sebastian Loeppmann; Jan Tegtmeier; Yijie Shi; Alberto Andrino de la Fuente; Jens Boy; Georg Guggenberger; Andreas Fulterer; Martin Fritsch; Sandra Spielvogel (Biology and Fertility of Soils, 2023)

Estimation of the Surface Fluxes for Heat and Momentum in Unstable Conditions with Machine Learning and Similarity Approaches for the LAFE Data Set - Volker Wulfmeyer; Juan Manuel Valencia Pineda; Sebastian Otte; Matthias Karlbauer; Martin V. Butz; Temple R. Lee; Verena Rajtschan (Boundary-Layer Meteorology, 2023)
Measurements of three flux towers operated during the land atmosphere feedback experiment (LAFE) are used to investigate relationships between surface fluxes and variables of the land–atmosphere system. We study these relations by means of two machine learning (ML) techniques: multilayer perceptrons (MLP) and extreme gradient boosting (XGB). We compare their flux derivation performance with Monin–Obukhov similarity theory (MOST) and a similarity relationship using the bulk Richardson number (BRN). The ML approaches outperform MOST and BRN. Best agreement with the observations is achieved for the friction velocity. For the sensible heat flux and even more so for the latent heat flux, MOST and BRN deviate from the observations while MLP and XGB yield more accurate predictions. Using MOST and BRN for latent heat flux, the root mean square errors (RMSE) are 107 Wm $$^{-2}$$ - 2 and 121 Wm $$^{-2}$$ - 2 , respectively, as well as the intercepts of the regression lines are $$≈ 110$$ ≈ 110 Wm $$^{-2}$$ - 2 . For the ML methods, the RMSEs reduce to 31 Wm $$^{-2}$$ - 2 for MLP and 33 Wm $$^{-2}$$ - 2 for XGB as well as the intercepts to just 4 Wm $$^{-2}$$ - 2 for MLP and $$-1$$ - 1 Wm $$^{-2}$$ - 2 for XGB with slopes of the regression lines close to 1, respectively. These results indicate significant deficiencies of MOST and BRN, particularly for the derivation of the latent heat flux. In fact, in contrast to the established theories, feature importance weighting demonstrates that the ML methods base their improved derivations on net radiation, the incoming and outgoing shortwave radiations, the air temperature gradient, and the available water contents, but not on the water vapor gradient. The results imply that further studies of surface fluxes and other turbulent variables with ML techniques provide great promise for deriving advanced flux parameterizations and their implementation in land–atmosphere system models.

Improving insect conservation management through insect monitoring and stakeholder involvement - Sebastian Köthe; Florian D. Schneider; Nikita Bakanov; Carsten A. Brühl; Lisa Eichler; Thomas Fickel; Birgit Gemeinholzer; Thomas Hörren; Alexandra Lux; Gotthard Meinel; Livia Schäffler; Christoph Scherber; et al. (Biodiversity and Conservation, 2023)
In recent years, the decline of insect biodiversity and the imminent loss of provided ecosystem functions and services has received public attention and raised the demand for political action. The complex, multi-causal contributors to insect decline require a broad interdisciplinary and cross-sectoral approach that addresses ecological and social aspects to find sustainable solutions. The project Diversity of Insects in Nature protected Areas (DINA) assesses insect communities in 21 nature reserves in Germany, and considers interactions with plant diversity, pesticide exposure, spatial and climatic factors. The nature reserves border on agricultural land, to investigate impacts on insect diversity. Part of the project is to obtain scientific data from Malaise traps and their surroundings, while another part involves relevant stakeholders to identify opportunities and obstacles to insect diversity conservation. Our results indicate a positive association between insect richness and biomass. Insect richness was negatively related to the number of stationary pesticides (soil and vegetation), pesticides measured in ethanol, the amount of area in agricultural production, and precipitation. Our qualitative survey along with stakeholder interviews show that there is general support for insect conservation, while at the same time the stakeholders expressed the need for more information and data on insect biodiversity, as well as flexible policy options. We conclude that conservation management for insects in protected areas should consider a wider landscape. Local targets of conservation management will have to integrate different stakeholder perspectives. Scientifically informed stakeholder dialogues can mediate conflicts of interests, knowledge, and values to develop mutual conservation scenarios.

Impacts of autochthonous particulate organic matter on redox-conditions and elimination of trace organic chemicals in managed aquifer recharge - Josefine Filter; Till Ermisch; Aki Sebastian Ruhl; Martin Jekel (Environmental Science and Pollution Research, 2023)
Autochthonous carbon fixation by algae and subsequent deposition of particulate organic matter can have significant effects on redox conditions and elimination of trace organic chemicals (TOrCs) in managed aquifer recharge (MAR). This study investigated the impacts of different algae loadings (0–160 g/m 2 ) and infiltration rates (0.06–0.37 m/d) on overall oxygen consumption and elimination of selected TOrCs (diclofenac, formylaminoantipyrine, gabapentin, and sulfamethoxazole) in adapted laboratory sand columns. An infiltration rate of 0.37 m/d in conjunction with an algae load of 80 g/m 2 (dry weight) sustained oxic conditions in the sand bed and did not affect the degradation of TOrCs. Thus, the availability of easily degradable organic carbon from algae did not influence the removal of TOrCs at an influent concentration of 1 µg/L. In contrast, a lower infiltration rate of 0.20 m/d in combination with a higher algae loading of 160 g/m 2 caused anoxic conditions for 30 days and significantly impeded the degradation of formylaminoantipyrine, gabapentin, sulfamethoxazole, and diclofenac. Especially the elimination of gabapentin did not fully recover within 130 days after pulsed algae deposition. Hence, measures like micro-sieving or nutrient control are required at bank filtration or soil aquifer treatment sites with low infiltration rates.

Disentangling drivers of litter decomposition in a multi-continent network of tree diversity experiments - Ellen Desie; Juan Zuo; Kris Verheyen; Ika Djukic; Koenraad Van Meerbeek; Harald Auge; Nadia Barsoum; Christel Baum; Helge Bruelheide; Nico Eisenhauer; Heike Feldhaar; Olga Ferlian; et al. (Science of The Total Environment, 2023)

Nano- and microplastics: a comprehensive review on their exposure routes, translocation, and fate in humans - Anja F.R.M. Ramsperger; Enrico Bergamaschi; Marco Panizzolo; Ivana Fenoglio; Francesco Barbero; Ruud Peters; Anna Undas; Sebastian Purker; Bernd Giese; Carina R. Lalyer; Alba Tamargo; M. Victoria Moreno-Arribas; et al. (NanoImpact, 2023)

Smaller human populations are neither a necessary nor sufficient condition for biodiversity conservation - Alice C. Hughes; Kévin Tougeron; Dominic A. Martin; Filippo Menga; Bruno H.P. Rosado; Sebastian Villasante; Shweta Madgulkar; Fernando Gonçalves; Davide Geneletti; Luisa Maria Diele-Viegas; Sebastian Berger; Sheila R. Colla; et al. (Biological Conservation, 2023)

The influence of viral infection on cell line characteristics: Lessons learned from working with new cell lines from common carp - Martin Felten; Mikolaj Adamek; Marina Gebert; Sebastian Rakers; Dieter Steinhagen (Journal of Fish Diseases, 2022)
Several factors influence the susceptibility of cell lines to infection by different viruses. These can be related to tissue specificity of the viruses, physiological status of the cells, their differentiation level and their capacity to mount immune responses to combat viral infection. To study the influence of cell characteristics and immune responses on their susceptibility on virus infection, newly developed cell lines from common carp brain (CCAbre), fins (CCApin), gills (CCAgill), and heart (CCAcar) and the established common carp brain (CCB) cells were exposed to the carp infecting viruses cyprinid herpesvirus 3 (CyHV‐3), carp oedema virus (CEV), and the yet not fully characterized common carp paramyxovirus (CCPV). The susceptibility of these cells to viral infection was measured by formation of a cytopathic effect (CPE), estimation of viral particles produced by the cells and presence of viral mRNA in the cells. Viral susceptibility of the cells was compared to cell characteristics, measured by mRNA expression of the epithelial cell markers cadherin 1, occludin, and cytokeratin 15 and the mesenchymal cell marker vimentin, as well as to the level of type I interferon (IFN) responses. All cell lines were susceptible to CyHV‐3 and CCPV but not to CEV infection. The cell lines had different levels of type I IFN responses towards the viruses. Typically, CyHV‐3 did not induce high type I IFN responses, while CCPV induced high responses in CCAbre, CCAcar, CCApin cells but no response in CCAgill cells. Consequently, the type I IFN response modulated cell susceptibility to CCPV but not to CyHV‐3. Interestingly, when the three different passage levels of CCB cells were examined, the susceptibility of one passage was significantly lower for CyHV‐3 and higher for CCPV infection. This coincided with a loss of epithelial markers and lower type I IFN responses. This study confirms an influence of cell characteristics and immune responses on the susceptibility of carp cell lines for virus infection. Depending on the vulnerability of the virus to type I IFN responses, cells with a lower IFN‐response can be superior for replication of some viruses. Batches of CCB cells can differentiate and thus may have significantly different levels of susceptibility to certain viruses.

Solving three major biases of the ETAS model to improve forecasts of the 2019 Ridgecrest sequence - Christian Grimm; Sebastian Hainzl; Martin Käser; Helmut Küchenhoff (Stochastic Environmental Research and Risk Assessment, 2022)
Strong earthquakes cause aftershock sequences that are clustered in time according to a power decay law, and in space along their extended rupture, shaping a typically elongate pattern of aftershock locations. A widely used approach to model earthquake clustering, the Epidemic Type Aftershock Sequence (ETAS) model, shows three major biases. First, the conventional ETAS approach assumes isotropic spatial triggering, which stands in conflict with observations and geophysical arguments for strong earthquakes. Second, the spatial kernel has unlimited extent, allowing smaller events to exert disproportionate trigger potential over an unrealistically large area. Third, the ETAS model assumes complete event records and neglects inevitable short-term aftershock incompleteness as a consequence of overlapping coda waves. These three aspects can substantially bias the parameter estimation and lead to underestimated cluster sizes. In this article, we combine the approach of Grimm et al. (Bulletin of the Seismological Society of America, 2021), who introduced a generalized anisotropic and locally restricted spatial kernel, with the ETAS-Incomplete (ETASI) time model of Hainzl (Bulletin of the Seismological Society of America, 2021), to define an ETASI space-time model with flexible spatial kernel that solves the abovementioned shortcomings. We apply different model versions to a triad of forecasting experiments of the 2019 Ridgecrest sequence, and evaluate the prediction quality with respect to cluster size, largest aftershock magnitude and spatial distribution. The new model provides the potential of more realistic simulations of on-going aftershock activity, e.g. allowing better predictions of the probability and location of a strong, damaging aftershock, which might be beneficial for short term risk assessment and disaster response.

The impact of NOx and SO2 emissions from a magnesite processing industry on morphophysiological and anatomical features of plant bioindicators - Katielle Silva Brito Kateivas; Paulo Araquém Ramos Cairo; Pedro Henrique Santos Neves; Roger Sebastian Silva Ribeiro; Leohana Martins Machado; Carlos André Espolador Leitão (Acta Physiologiae Plantarum, 2022)

Sedimentation history of Lake Taymyr, Central Russian Arctic, since the Last Glacial Maximum - Raphael Gromig; Elodie Lebas; Larisa Savelieva; Zina Pushina; Grigory Fedorov; Dominik Brill; Marlene Margit Lenz; Sebastian Krastel; Bernd Wagner; Nataliya Kostromina; Mark Mustafin; Martin Melles (Journal of Quaternary Science, 2022)
Hydro‐acoustic and seismic data and 2‐ to 16‐m‐long sediment cores from the central area of Lake Taymyr (Taymyr Peninsula, central Russian Arctic) were investigated to reconstruct its sedimentation history. Granulometric, chronological, geochemical and biological data from the sediment cores reveal two lowstands and two highstands of the lake level, which is today located ca. 5 m above sea level during summer. Our study confirms the presence of an ice sheet blocking the drainage of Lake Taymyr during the latest Weichselian. Although chronological control of the sediment cores does not allow us to unambiguously constrain the time frame for each of the lake stages, the proposed timing of events is in good agreement with regional terrestrial archives as well as marine signals on the Kara Sea Shelf. Overall, the data show that the evolution of Lake Taymyr involved a complex interplay of regional climatic, glacial and sea‐level changes.

Highly variable sediment deposition in Lake Imandra, NW Russia, since the Late Pleistocene - Matthias Lenz; Elodie Lebas; Marlene M. Lenz; Grigory Fedorov; Raphael Gromig; Vasili Kolka; Sebastian Krastel; Niklas Leicher; Martin Melles; Bernd Wagner (Journal of Quaternary Science, 2022)
To understand the dynamics of sediment deposition and the potential influences of complex current systems in large lakes, Lake Imandra (Kola Peninsula) has been investigated. Seismic and echo‐sounder data of the central part of Bolshaya Imandra reveal the sediment architecture in unprecedented detail. In addition, the sediment core data indicate highly variable depositional processes since the Late Pleistocene. The complex morphology of the lacustrine basin favoured accumulation of sediment in depressions, where they were preserved from erosion. Three main stratigraphic units (SU I–III) were identified above the acoustic basement. The oldest SU III is best preserved along a tectonic trench and interpreted as glacial deposits partly eroded by the Scandinavian Ice Sheet during Marine Isotope Stage (MIS) 2. The overlying SU II deposits are regarded as a till related to MIS 2 glaciation. The youngest SU I represents glaciofluvial, glaciolacustrine and lacustrine sediment deposited after ice retreat. As the north–south‐trending main axis of Bolshaya Imandra runs parallel to the predominant wind direction, the basin is subject to strong wind‐induced surficial currents and compensatory subsurface currents. These currents occur in water depth of 0–15 and deeper than 30 m, respectively, and their velocity prevents sediment accumulation.

Climate and environmental history at Lake Levinson‐Lessing, Taymyr Peninsula, during the last 62 kyr - Matthias Lenz; Marlene M. Lenz; Andrei Andreev; Stephanie Scheidt; Raphael Gromig; Elodie Lebas; Grigory Fedorov; Sebastian Krastel; Martin Melles; Bernd Wagner (Journal of Quaternary Science, 2022)
The 45.95 m‐long sediment succession shown in core Co1401 from Lake Levinson‐Lessing allows the reconstruction of the largely unexplored environmental and climatic history of the Taymyr Peninsula of the past 62 kyr. The core was analysed with a multidisciplinary approach including lithological, granulometric, geochemical and pollen analyses. The proxy data indicate a relatively stable, herb‐dominated environment with only subtle changes between a cold/wet late Marine Isotope Stage (MIS) 4 and early MIS 3, mild/dry middle and late MIS 3 and a cold/dry MIS 2. The absence of pronounced climate fluctuations demonstrates that the Lake Levinson‐Lessing catchment was not covered by an ice sheet during this period. Changes in precipitation were likely caused by waxing and waning of the large Eurasian ice sheets outside of the Taymyr Peninsula, which changed the eastward moisture transport and atmospheric circulation patterns. MIS 1 at Lake Levinson‐Lessing was associated with overall warmer and wetter conditions and short‐term climate fluctuations during the Bølling–Allerød warming, Younger Dryas cooling and Preboreal transition, which indicates the influence of North Atlantic air masses.

Vepris onanae (Rutaceae), a new Critically Endangered cloud-forest tree species, and the endemic plant species of Bali Ngemba Forest Reserve, Bamenda Highlands Cameroon - Martin Cheek; Sebastian Hatt; Jean Michel Onana (Kew Bulletin, 2022)
Summary We revise and update the records of strict and near-endemic species of the Bali Ngemba Forest Reserve, the largest known surviving patch (c. 8 km 2 in area) of submontane or cloud forest in the Bamenda Highlands, Cameroon which have lost >96 % of their original forest due to human activities. Nine strict endemics, and 11 near endemics are now documented, a drop from the number recorded after the first survey in 2004, since when five of the provisionally named species have been validly published. We test the hypothesis that a further one of the provisionally named putative Bali Ngemba new species, Vepris sp. A, an 8 – 20 m tall tree from cloud forest in the 1310 – 1700 m altitudinal band, is indeed new to science. We compare it morphologically with other multicarpellate, apocarpous, trifoliolate Cameroon tree species formerly placed in the genus Oricia Pierre until they were subsumed into Vepris by Mziray (1992). These are V. trifoliolata (Engl.) Mziray and V. gabonensis (Pierre) Mziray. We conclude that Vepris sp. A is a new undescribed species here named as Vepris onanae . The new species is illustrated, mapped and its conservation status assessed as Critically Endangered using the 2012 IUCN standard due to severe fragmentation and the threats of habitat clearance from agricultural pressures at its three locations all of which remain formally unprotected. Vepris onanae appears unique among the Guineo-Congolian African oricioid species of Vepris in that it occurs in cloud forest, the other species, apart from V. renieri (G.C.C.Gilbert) Mziray of the Albertine Rift, occurring in lowland forest. It also differs in the very broad, (7.8 –) 11.3 – 18 cm wide leaflets of the flowering stems which have a 6 – 18 (– 30) mm long, narrowly triangular acumen (vs leaflets <12 cm wide, acumen absent or short) and in having both subsessile and pedicellate (pedicels 0.25 – 0.3 mm long and 1 (– 2) mm long) male flowers (vs male flower pedicels all sessile, or all c. 3 mm long). We report for the first time on stage-dependent leaf heteromorphy in Vepris and characterise a level of sexual dimorphism more advanced than usual in the genus. We highlight the importance of protecting Bali Ngemba and other forest patches in the Bamenda Highlands if species such as Vepris onanae are not soon to become extinct.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

When to Extend Monitoring of Anti-drug Antibodies for High-risk Biotherapeutics in Clinical Trials: an Opinion from the European Immunogenicity Platform - Gregor P. Lotz; Karin Benstein; Karien Bloem; Harm Buddiger; Claudio Calonder; Stefanie Elm; Elena Fernandez; Joanne Goodman; Boris Gorovits; Joanna Grudzinska-Goebel; Melody Janssen; Vibha Jawa; et al. (The AAPS Journal, 2022)
The determination of a tailored anti-drug antibody (ADA) testing strategy is based on the immunogenicity risk assessment to allow a correlation of ADAs with changes to pharmacokinetics, efficacy, and safety. The clinical impact of ADA formation refines the immunogenicity risk assessment and defines appropriate risk mitigation strategies. Health agencies request for high-risk biotherapeutics to extend ADA monitoring for patients that developed an ADA response to the drug until ADAs return to baseline levels. However, there is no common understanding in which cases an extension of ADA follow-up sampling beyond the end of study (EOS) defined in the clinical study protocol is required. Here, the Immunogenicity Strategy Working Group of the European Immunogenicity Platform (EIP) provides recommendations on requirements for an extension of ADA follow-up sampling in clinical studies where there is a high risk of serious consequences from ADAs. The importance of ADA evaluation during a treatment-free period is recognized but the decision whether to extend ADA monitoring at a predefined EOS should be based on evaluation of ADA data in the context of corresponding clinical signals. If the clinical data set shows that safety consequences are minor, mitigated, or resolved, further ADA monitoring may not be required despite potentially detectable ADAs above baseline. Extended ADA monitoring should be centered on individual patient benefit.

Assessment of defoliation and subsequent growth losses caused by Lymantria dispar using terrestrial laser scanning (TLS) - Martin Jacobs; Torben Hilmers; Benjamin M. L. Leroy; Hannes Lemme; Sebastian Kienlein; Jörg Müller; Wolfgang W. Weisser; Hans Pretzsch (Trees, 2022)
Key message TLS scans of three surveys before, during and after gypsy moth gradation, allowed high-resolution tracking of defoliation and subsequent inter-annual growth losses on an individual tree level. Abstract Foliation strongly determines all tree growth processes but can be reduced by various stress factors. Insect defoliation starts at variable times and is one stress factor that may affect photosynthetic processes and cause immediate reactions like refoliation, which are difficult to detect by surveys repeated at 1-year intervals. This study used a large-scale field experiment in German oak/mixed forests affected by gypsy moths ( Lymantria dispar ) to test the use of terrestrial laser scanning (TLS) for detecting inter-annual foliation and growth losses at the individual tree level caused by the gypsy moth. The experiment comprised two levels of gypsy moth defoliation risk, high (H) and low (L), as well as two pest control treatment levels: spraying with the insecticide Mimic (M) or unsprayed control (C). The factorial design consisted of four treatment combinations (HC, HM, LC, and LM), applied to 11 spatial blocks with a total of 44 plots. The TLS approach detected the defoliation caused by the gypsy moth, estimated as leaf area and crown perforation parameters. For the first time, TLS-derived tree foliation was evaluated based on inter-annual stem growth. Leaf area and crown perforation showed a correlation of + 0.6 and – 0.35, respectively, with basal area increments. Furthermore, this study revealed subsequent growth losses in the same year due to defoliation. Our results show that TLS can offer new opportunities to develop new indicators that monitor foliation at the individual tree level. The crown perforation can describe defoliation or the tree’s vitality based on one scanning campaign, whereas the leaf area needed at least two.

Who gets prescriptions for proton pump inhibitors and why? A drug-utilization study with claims data in Bavaria, Germany, 2010–2018 - Ina-Maria Rückert-Eheberg; Michael Nolde; Nayeon Ahn; Martin Tauscher; Roman Gerlach; Florian Güntner; Alexander Günter; Christa Meisinger; Jakob Linseisen; Ute Amann; Sebastian-Edgar Baumeister (European Journal of Clinical Pharmacology, 2022)
Purpose The German annual drug prescription-report has indicated overuse of proton pump inhibitors (PPIs) for many years; however, little was known about the characteristics of people using PPIs. This study aimed to provide comprehensive utilization data and describe frequencies of potential on- and off-label PPI-indications in Bavaria, Germany. Methods Claims data of statutorily insured people from 2010 to 2018 were used. Defined daily doses (DDDs) of PPIs by type of drug, prevalence of PPI-use and DDDs prescribed per 1000 insured people/day were analyzed. For 2018, proportions of users and DDDs per 1000 insured people were calculated by age and sex. To elucidate changes in prescribing practices due to a suspected drug-drug interaction, we examined co-prescribing of clopidogrel and PPIs between 2010 and 2018. For PPI new users, sums of DDDs and frequencies of potential indications were examined. Results PPI prescribing increased linearly from 2010 to 2016 and gradually decreased from 2016 to 2018. In 2018, 14.7% of women and 12.2% of men received at least one prescription, and 64.8 DDDs (WHO-def.) per 1000 insured people/day were prescribed. Overall, omeprazole use decreased over the observation period and was steadily replaced by pantoprazole, especially when co-prescibed with clopidogrel. An on-label PPI-indication was not reported at first intake in 52.0% of new users. Conclusions The utilization of prescribed PPIs has decreased since 2016. However, a large proportion of new PPI-users had no documentation of a potential indication, and the sums of DDDs prescribed often seemed not to comply with guidelines.

Oxidative effects on Ri T-DNA-transformed root of Daucus carota exposed to anthracene - Romina Storb; Elisabet Aranda; Sebastian Fracchia; Nahuel Spinedi; José Martin Scervino (Theoretical and Experimental Plant Physiology, 2022)

Projecting coral responses to intensifying marine heatwaves under ocean acidification - Shannon G. Klein; Nathan R. Geraldi; Andrea Anton; Sebastian Schmidt‐Roach; Maren Ziegler; Maha J. Cziesielski; Cecilia Martin; Nils Rädecker; Thomas L. Frölicher; Peter J. Mumby; John M. Pandolfi; David J. Suggett; et al. (Global Change Biology, 2022)
Over this century, coral reefs will run the gauntlet of climate change, as marine heatwaves (MHWs) become more intense and frequent, and ocean acidification (OA) progresses. However, we still lack a quantitative assessment of how, and to what degree, OA will moderate the responses of corals to MHWs as they intensify throughout this century. Here, we first projected future MHW intensities for tropical regions under three future greenhouse gas emissions scenario (representative concentration pathways, RCP2.6, RCP4.5 and RCP8.5) for the near‐term (2021–2040), mid‐century (2041–2060) and late‐century (2081–2100). We then combined these MHW intensity projections with a global data set of 1,788 experiments to assess coral attribute performance and survival under the three emissions scenarios for the near‐term, mid‐century and late‐century in the presence and absence of OA. Although warming and OA had predominately additive impacts on the coral responses, the contribution of OA in affecting most coral attributes was minor relative to the dominant role of intensifying MHWs. However, the addition of OA led to greater decreases in photosynthesis and survival under intermediate and unrestricted emissions scenario for the mid‐ and late‐century than if intensifying MHWs were considered as the only driver. These results show that role of OA in modulating coral responses to intensifying MHWs depended on the focal coral attribute and extremity of the scenario examined. Specifically, intensifying MHWs and OA will cause increasing instances of coral bleaching and substantial declines in coral productivity, calcification and survival within the next two decades under the low and intermediate emissions scenario. These projections suggest that corals must rapidly adapt or acclimatize to projected ocean conditions to persist, which is far more likely under a low emissions scenario and with increasing efforts to manage reefs to enhance resilience.

Correction to: Genetic and Clinical Predictors of Ataxia in Pediatric Primary Mitochondrial Disorders - Juan Sebastian Martin‑Saavedra; Sara Reis Teixeira; Cesar Augusto Pinheiro Ferreira Alves; Fabrício Guimarães Gonçalves; Luis Octavio Tierradentro‑Garcia; Martin Kidd; Colleen Muraresku; ·Amy Goldstein; Arastoo Vossough (The Cerebellum, 2022)

Genetic and Clinical Predictors of Ataxia in Pediatric Primary Mitochondrial Disorders - Juan Sebastian Martin-Saavedra; Sara Reis Teixeira; Cesar Augusto Pinheiro Ferreira Alves; Fabrício Guimarães Gonçalves; Luis Octavio Tierradentro-García; Martin Kidd; Colleen Muraresku; Amy Goldstein; Arastoo Vossough (The Cerebellum, 2022)

Integrating environmental variability to broaden the research on coral responses to future ocean conditions - Maren Ziegler; Andrea Anton; Shannon G. Klein; Nils Rädecker; Nathan R. Geraldi; Sebastian Schmidt‐Roach; Vincent Saderne; Peter J. Mumby; Maha J. Cziesielski; Cecilia Martin; Thomas L. Frölicher; John M. Pandolfi; et al. (Global Change Biology, 2021)
Our understanding of the response of reef‐building corals to changes in their physical environment is largely based on laboratory experiments, analysis of long‐term field data, and model projections. Experimental data provide unique insights into how organisms respond to variation of environmental drivers. However, an assessment of how well experimental conditions cover the breadth of environmental conditions and variability where corals live successfully is missing. Here, we compiled and analyzed a globally distributed dataset of in‐situ seasonal and diurnal variability of key environmental drivers (temperature, p CO 2 , and O 2 ) critical for the growth and livelihood of reef‐building corals. Using a meta‐analysis approach, we compared the variability of environmental conditions assayed in coral experimental studies to current and projected conditions in their natural habitats. We found that annual temperature profiles projected for the end of the 21st century were characterized by distributional shifts in temperatures with warmer winters and longer warm periods in the summer, not just peak temperatures. Furthermore, short‐term hourly fluctuations of temperature and p CO 2 may regularly expose corals to conditions beyond the projected average increases for the end of the 21st century. Coral reef sites varied in the degree of coupling between temperature, p CO 2 , and dissolved O 2 , which warrants site‐specific, differentiated experimental approaches depending on the local hydrography and influence of biological processes on the carbonate system and O 2 availability. Our analysis highlights that a large portion of the natural environmental variability at short and long timescales is underexplored in experimental designs, which may provide a path to extend our understanding on the response of corals to global climate change.

Diversity of Insects in Nature protected Areas (DINA): an interdisciplinary German research project - Gerlind U. C. Lehmann; Nikita Bakanov; Martin Behnisch; Sarah J. Bourlat; Carsten A. Brühl; Lisa Eichler; Thomas Fickel; Matthias F. Geiger; Birgit Gemeinholzer; Thomas Hörren; Sebastian Köthe; Alexandra Lux; et al. (Biodiversity and Conservation, 2021)
Insect declines and biodiversity loss have attracted much attention in recent years, but lack of comprehensive data, conflicting interests among stakeholders and insufficient policy guidance hinder progress in preserving biodiversity. The project DINA (Diversity of Insects in Nature protected Areas) investigates insect communities in 21 nature reserves in Germany. All selected conservation sites border arable land, with agricultural practices assumed to influence insect populations. We taught citizen scientists how to manage Malaise traps for insect collection, and subsequently used a DNA metabarcoding approach for species identification. Vegetation surveys, plant metabarcoding as well as geospatial and ecotoxicological analyses will help to unravel contributing factors for the deterioration of insect communities. As a pioneering research project in this field, DINA includes a transdisciplinary dialogue involving relevant stakeholders such as local authorities, policymakers, and farmers, which aims at a shared understanding of conservation goals and action pathways. Stakeholder engagement combined with scientific results will support the development of sound policy recommendations to improve legal frameworks, landscape planning, land use, and conservation strategies. With this transdisciplinary approach, we aim to provide the background knowledge to implement policy strategies that will halt further decline of insects in German protected areas.

First record of the soybean stem fly Melanagromyza sojae (Diptera: Agromyzidae) in chickpea crops - Martin Alejandro Vera; Clerison Regis Perini; Maria Gabriela Murúa; Augusto Sebastian Casmuz; Gerardo Gastaminza; Jerson Carus Guedes (International Journal of Tropical Insect Science, 2021)

Animal-Mediated Ecosystem Process Rates in Forests and Grasslands are Affected by Climatic Conditions and Land-Use Intensity - Didem Ambarlı; Nadja K. Simons; Katja Wehner; Wiebke Kämper; Martin M. Gossner; Thomas Nauss; Felix Neff; Sebastian Seibold; Wolfgang Weisser; Nico Blüthgen (Ecosystems, 2021)
Decomposition, vegetation regeneration, and biological control are essential ecosystem functions, and animals are involved in the underlying processes, such as dung removal, seed removal, herbivory, and predation. Despite evidence for declines of animal diversity and abundance due to climate change and land-use intensification, we poorly understand how animal-mediated processes respond to these global change drivers. We experimentally measured rates of four ecosystem processes in 134 grassland and 149 forest plots in Germany and tested their response to climatic conditions and land-use intensity, that is, grazing, mowing, and fertilization in grasslands and the proportion of harvested wood, non-natural trees, and deadwood origin in forests. For both climate and land use, we distinguished between short-term effects during the survey period and medium-term effects during the preceding years. Forests had significantly higher process rates than grasslands. In grasslands, the climatic effects on the process rates were similar or stronger than land-use effects, except for predation; land-use intensity negatively affected several process rates. In forests, the land-use effects were more pronounced than the climatic effects on all processes except for predation. The proportion of non-natural trees had the greatest impact on the process rates in forests. The proportion of harvested wood had negative effects, whereas the proportion of anthropogenic deadwood had positive effects on some processes. The effects of climatic conditions and land-use intensity on process rates mirror climatic and habitat effects on animal abundance, activity, and resource quality. Our study demonstrates that land-use changes and interventions affecting climatic conditions will have substantial impacts on animal-mediated ecosystem processes.

The GenTree Leaf Collection: Inter‐ and intraspecific leaf variation in seven forest tree species in Europe - Raquel Benavides; Bárbara Carvalho; Cristina C. Bastias; David López‐Quiroga; Antonio Mas; Stephen Cavers; Alan Gray; Audrey Albet; Ricardo Alía; Olivier Ambrosio; Filippos Aravanopoulos; Francisco Auñón; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait variation within species can reveal plastic and/or genetic responses to environmental gradients, and may indicate where local adaptation has occurred. Here, we present a dataset of rangewide variation in leaf traits from seven of the most ecologically and economically important tree species in Europe. Sample collection and trait assessment are embedded in the GenTree project (EU‐Horizon 2020), which aims at characterizing the genetic and phenotypic variability of forest tree species to optimize the management and sustainable use of forest genetic resources. Our dataset captures substantial intra‐ and interspecific leaf phenotypic variability, and provides valuable information for studying the relationship between ecosystem functioning and trait variability of individuals, and the response and resilience of species to environmental changes. Main types of variable contained We chose morphological and chemical characters linked to trade‐offs between acquisition and conservation of resources and water use, namely specific leaf area, leaf size, carbon and nitrogen content and their ratio, and the isotopic signature of stable isotope 13 C and 15 N in leaves. Spatial location and grain We surveyed between 18 and 22 populations per species, 141 in total, across Europe. Time period Leaf sampling took place between 2016 and 2017. Major taxa and level of measurement We sampled at least 25 individuals in each population, 3,569 trees in total, and measured traits in 35,755 leaves from seven European tree species, i.e. the conifers Picea abies , Pinus pinaster and Pinus sylvestris , and the broadleaves Betula pendula , Fagus sylvatica , Populus nigra and Quercus petraea . Software format The data files are in ASCII text, tab delimited, not compressed.

A research perspective towards a more complete biodiversity footprint: a report from the World Biodiversity Forum - Alexandra Marques; Marine Robuchon; Stefanie Hellweg; Tim Newbold; Jutta Beher; Sebastian Bekker; Franz Essl; Daniele Ehrlich; Samantha Hill; Martin Jung; Sandra Marquardt; Francesca Rosa; et al. (The International Journal of Life Cycle Assessment, 2021)

Investing in Blue Natural Capital to Secure a Future for the Red Sea Ecosystems - Maha J. Cziesielski; Carlos M. Duarte; Nojood Aalismail; Yousef Al-Hafedh; Andrea Anton; Faiyah Baalkhuyur; Andrew C. Baker; Thorsten Balke; Iliana B. Baums; Michael Berumen; Vasiliki I. Chalastani; Brendan Cornwell; et al. (Frontiers in Marine Science, 2021)
For millennia, coastal and marine ecosystems have adapted and flourished in the Red Sea’s unique environment. Surrounded by deserts on all sides, the Red Sea is subjected to high dust inputs and receives very little freshwater input, and so harbors a high salinity. Coral reefs, seagrass meadows, and mangroves flourish in this environment and provide socio-economic and environmental benefits to the bordering coastlines and countries. Interestingly, while coral reef ecosystems are currently experiencing rapid decline on a global scale, those in the Red Sea appear to be in relatively better shape. That said, they are certainly not immune to the stressors that cause degradation, such as increasing ocean temperature, acidification and pollution. In many regions, ecosystems are already severely deteriorating and are further threatened by increasing population pressure and large coastal development projects. Degradation of these marine habitats will lead to environmental costs, as well as significant economic losses. Therefore, it will result in a missed opportunity for the bordering countries to develop a sustainable blue economy and integrate innovative nature-based solutions. Recognizing that securing the Red Sea ecosystems’ future must occur in synergy with continued social and economic growth, we developed an action plan for the conservation, restoration, and growth of marine environments of the Red Sea. We then investigated the level of resources for financial and economic investment that may incentivize these activities. This study presents a set of commercially viable financial investment strategies, ecological innovations, and sustainable development opportunities, which can, if implemented strategically, help ensure long-term economic benefits while promoting environmental conservation. We make a case for investing in blue natural capital and propose a strategic development model that relies on maintaining the health of natural ecosystems to safeguard the Red Sea’s sustainable development.

Viscoelasticity of striatal brain areas reflects variations in body mass index of lean to overweight male adults - Stefan Hetzer; Sebastian Hirsch; Jürgen Braun; Ingolf Sack; Martin Weygandt (Brain Imaging and Behavior, 2020)

Ecosystem transpiration and evaporation: Insights from three water flux partitioning methods across FLUXNET sites - Jacob A. Nelson; Oscar Pérez‐Priego; Sha Zhou; Rafael Poyatos; Yao Zhang; Peter D. Blanken; Teresa E. Gimeno; Georg Wohlfahrt; Ankur R. Desai; Beniamino Gioli; Jean‐Marc Limousin; Damien Bonal; et al. (Global Change Biology, 2020)
We apply and compare three widely applicable methods for estimating ecosystem transpiration ( T ) from eddy covariance (EC) data across 251 FLUXNET sites globally. All three methods are based on the coupled water and carbon relationship, but they differ in assumptions and parameterizations. Intercomparison of the three daily T estimates shows high correlation among methods ( R between .89 and .94), but a spread in magnitudes of T /ET (evapotranspiration) from 45% to 77%. When compared at six sites with concurrent EC and sap flow measurements, all three EC‐based T estimates show higher correlation to sap flow‐based T than EC‐based ET. The partitioning methods show expected tendencies of T /ET increasing with dryness (vapor pressure deficit and days since rain) and with leaf area index (LAI). Analysis of 140 sites with high‐quality estimates for at least two continuous years shows that T /ET variability was 1.6 times higher across sites than across years. Spatial variability of T /ET was primarily driven by vegetation and soil characteristics (e.g., crop or grass designation, minimum annual LAI, soil coarse fragment volume) rather than climatic variables such as mean/standard deviation of temperature or precipitation. Overall, T and T /ET patterns are plausible and qualitatively consistent among the different water flux partitioning methods implying a significant advance made for estimating and understanding T globally, while the magnitudes remain uncertain. Our results represent the first extensive EC data‐based estimates of ecosystem T permitting a data‐driven perspective on the role of plants’ water use for global water and carbon cycling in a changing climate.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Rapid decline of Zika virus NS1 antigen-specific antibody responses, northeastern Brazil - Andres Moreira-Soto; Gilmara de Souza Sampaio; Célia Pedroso; Ignacio Postigo-Hidalgo; Beatrice Sarah Berneck; Sebastian Ulbert; Carlos Brites; Eduardo Martins Netto; Jan Felix Drexler (Virus Genes, 2020)
Zika virus (ZIKV) is a positive-stranded RNA virus within the Flaviviridae family. After decades of circulation in Asia, ZIKV was introduced to Brazil in 2014–2015, associated with a rise in congenital malformations. Unlike the genetically related dengue virus (DENV), ZIKV constitutes only one serotype. Although assumed that ZIKV infection may engender lifelong immunity, the long-term kinetics of ZIKV antibody responses are unclear. We assessed long-term kinetics of ZIKV NS1-IgG response in 144 individuals from 3 different subpopulations: HIV patients, tuberculosis patients and healthy individuals first tested in 2016 and retested 1.5–2 years after the 2015–2016 ZIKV epidemic in Salvador de Bahia, Brazil, using a widely distributed NS1-based commercial ELISA. The seropositivity in 2016 reached 59.0% (85/144, 95% confidence interval (CI) 50.7–66.7%), and decreased to 38.6% (56/144, CI 31.3–47.0%) 1.5–2 years later. In addition, the median ZIKV NS1-ELISA reactivity for individuals that remained positive in both timepoints significantly decreased from a ratio of 4.4 (95% CI 3.8–5.0) to 1.6 (95% CI 1.6–1.9) over the 2-year interval ( Z : − 6.1; p < 0.001) irrespective of the subpopulation analyzed. Initial 2016 DENV antibody response was non-significant between groups, suggesting comparable DENV background. The high 20.6% seroreversion suggest that widely used serologic tests may fail to account a considerable proportion of past ZIKV infections in flavivirus endemic countries. In addition, ZIKV immunity might be shorter-lived than previously thought, which may contribute to local ZIKV resurgence once individual immune responses wane sufficiently to reduce community protective immunity in addition to birth and migration.

Are lizards capable of inhibitory control? Performance on a semi-transparent version of the cylinder task in five species of Australian skinks - Birgit Szabo; Sebastian Hoefer; Martin J. Whiting (Behavioral Ecology and Sociobiology, 2020)
Inhibitory control, the inhibition of prepotent actions, is essential for higher-order cognitive processes such as planning, reasoning, and self-regulation. Individuals and species differ in inhibitory control. Identifying what influences inhibitory control ability within and between species is key to understanding how it evolved. We compared performance in the cylinder task across five lizard species: tree skinks ( Egernia striolata ), gidgee skinks ( Egernia stokesii ), eastern blue-tongue skinks ( Tiliqua s. scincoides ), sleepy lizards ( Tiliqua r. asper ), and eastern water skinks ( Eulamprus quoyii ). In our task, animals had to inhibit the prepotent motor response of directly approaching a reward placed within a semi-transparent mesh cylinder and instead reach in through the side openings. Additionally, in three lizard species, we compared performance in the cylinder task to reversal learning to determine the task specificity of inhibitory ability. Within species, neither sex, origin, body condition, neophobia, nor pre-experience with other cognitive tests affected individual performance. Species differed in motor response inhibition: Blue-tongue skinks made fewer contacts with the semi-transparent cylinder wall than all other species. Blue-tongue skinks also had lower body condition than the other species which suggest motivation as the underlying cause for species differences in task performance. Moreover, we found no correlation between inhibitory ability across different experiments. This is the first study comparing cylinder task performance among lizard species. Given that inhibitory control is probably widespread in lizards, motor response inhibition as exercised in the cylinder task appears to have a long evolutionary history and is likely fundamental to survival and fitness. Significance The study of lizard cognition is receiving increasing attention. Lizards are a diverse group with a wide range of ecological attributes and represent a model system through which we can test a wide range of hypotheses relating to cognitive evolution. Furthermore, considering their evolutionary history, studying non-avian reptile cognition can help understand the evolution of different cognitive abilities including inhibitory control. Here, we provide a comparison of inhibitory control ability in five lizard species. Consequently, we are able to, firstly, validate a method (the cylinder task) initially developed for the use in mammals and birds, for use in lizards, and secondly, collect valuable data on inhibitory control in a poorly studied group with respect to cognitive ability. Our study suggests non-cognitive factors as a major influence on cylinder task performance, which is in agreement with previous studies of other vertebrates.

Causes of slowing‐down seasonal CO 2 amplitude at Mauna Loa - Kai Wang; Yilong Wang; Xuhui Wang; Yue He; Xiangyi Li; Ralph F. Keeling; Philippe Ciais; Martin Heimann; Shushi Peng; Frédéric Chevallier; Pierre Friedlingstein; Stephen Sitch; et al. (Global Change Biology, 2020)
Changing amplitude of the seasonal cycle of atmospheric CO 2 (SCA) in the northern hemisphere is an emerging carbon cycle property. Mauna Loa (MLO) station (20°N, 156°W), which has the longest continuous northern hemisphere CO 2 record, shows an increasing SCA before the 1980s ( p 2 fertilization. This challenges the view that CO 2 fertilization is the dominant cause of emergent SCA trends at northern sites south of 40°N. The contribution of agricultural intensification on the deceleration of SCA at MLO was elusive according to land–atmosphere CO 2 flux estimated by DGVMs and atmospheric inversions. Our results also show the necessity to adequately account for changing circulation patterns in understanding carbon cycle dynamics observed from atmospheric observations and in using these observations to benchmark DGVMs.

Rainfall manipulation experiments as simulated by terrestrial biosphere models: Where do we stand? - Athanasios Paschalis; Simone Fatichi; Jakob Zscheischler; Philippe Ciais; Michael Bahn; Lena Boysen; Jinfeng Chang; Martin De Kauwe; Marc Estiarte; Daniel Goll; Paul J. Hanson; Anna B. Harper; et al. (Global Change Biology, 2020)
Changes in rainfall amounts and patterns have been observed and are expected to continue in the near future with potentially significant ecological and societal consequences. Modelling vegetation responses to changes in rainfall is thus crucial to project water and carbon cycles in the future. In this study, we present the results of a new model‐data intercomparison project, where we tested the ability of 10 terrestrial biosphere models to reproduce the observed sensitivity of ecosystem productivity to rainfall changes at 10 sites across the globe, in nine of which, rainfall exclusion and/or irrigation experiments had been performed. The key results are as follows: (a) Inter‐model variation is generally large and model agreement varies with timescales. In severely water‐limited sites, models only agree on the interannual variability of evapotranspiration and to a smaller extent on gross primary productivity. In more mesic sites, model agreement for both water and carbon fluxes is typically higher on fine (daily–monthly) timescales and reduces on longer (seasonal–annual) scales. (b) Models on average overestimate the relationship between ecosystem productivity and mean rainfall amounts across sites (in space) and have a low capacity in reproducing the temporal (interannual) sensitivity of vegetation productivity to annual rainfall at a given site, even though observation uncertainty is comparable to inter‐model variability. (c) Most models reproduced the sign of the observed patterns in productivity changes in rainfall manipulation experiments but had a low capacity in reproducing the observed magnitude of productivity changes. Models better reproduced the observed productivity responses due to rainfall exclusion than addition. (d) All models attribute ecosystem productivity changes to the intensity of vegetation stress and peak leaf area, whereas the impact of the change in growing season length is negligible. The relative contribution of the peak leaf area and vegetation stress intensity was highly variable among models.

Journal Club - Fabian M. Commichau; Jannis Anstatt; Sven Krappmann; Evi Stegmann; Sebastian Banhart; Kai Papenfort; Sascha Brunke; Bernhard Hube; Marc Bramkamp; Miriam Herbert; Johannes Sander; Jonathan Wolf Mueller; et al. (BIOspektrum, 2020)

Prospects and challenges of multi-omics data integration in toxicology - Sebastian Canzler; Jana Schor; Wibke Busch; Kristin Schubert; Ulrike E. Rolle-Kampczyk; Hervé Seitz; Hennicke Kamp; Martin von Bergen; Roland Buesen; Jörg Hackermüller (Archives of Toxicology, 2020)
Exposure of cells or organisms to chemicals can trigger a series of effects at the regulatory pathway level, which involve changes of levels, interactions, and feedback loops of biomolecules of different types. A single-omics technique, e.g., transcriptomics, will detect biomolecules of one type and thus can only capture changes in a small subset of the biological cascade. Therefore, although applying single-omics analyses can lead to the identification of biomarkers for certain exposures, they cannot provide a systemic understanding of toxicity pathways or adverse outcome pathways. Integration of multiple omics data sets promises a substantial improvement in detecting this pathway response to a toxicant, by an increase of information as such and especially by a systemic understanding. Here, we report the findings of a thorough evaluation of the prospects and challenges of multi-omics data integration in toxicological research. We review the availability of such data, discuss options for experimental design, evaluate methods for integration and analysis of multi-omics data, discuss best practices, and identify knowledge gaps. Re-analyzing published data, we demonstrate that multi-omics data integration can considerably improve the confidence in detecting a pathway response. Finally, we argue that more data need to be generated from studies with a multi-omics-focused design, to define which omics layers contribute most to the identification of a pathway response to a toxicant.

Maturation-related changes in the development and etiology of neuromuscular fatigue - Enzo Piponnier; Vincent Martin; Pierre Bourdier; Brice Biancarelli; Virginie Kluka; Sebastian Garcia-Vicencio; Anne-Gaëlle Jegu; Charlotte Cardenoux; Cédric Morio; Emmanuel Coudeyre; Sébastien Ratel (European Journal of Applied Physiology, 2019)

Towards a pro-resolving concept in systemic lupus erythematosus - Sebastian Boeltz; Melanie Hagen; Jasmin Knopf; Aparna Mahajan; Maximilian Schick; Yi Zhao; Cornelia Erfurt-Berge; Jürgen Rech; Luis E. Muñoz; Martin Herrmann (Seminars in Immunopathology, 2019)

The class II benzoyl‐coenzyme A reductase complex from the sulfate‐reducing Desulfosarcina cetonica - Sebastian E. L. Anselmann; Claudia Löffler; Hans‐Joachim Stärk; Nico Jehmlich; Martin von Bergen; Thomas Brüls; Matthias Boll (Environmental Microbiology, 2019)
Summary Benzoyl‐CoA reductases (BCRs) catalyse a key reaction in the anaerobic degradation pathways of monocyclic aromatic substrates, the dearomatization of benzoyl‐CoA (BzCoA) to cyclohexa‐1,5‐diene‐1‐carboxyl‐CoA (1,5‐dienoyl‐CoA) at the negative redox potential limit of diffusible enzymatic substrate/product couples ( E °′ = −622 mV). A 1‐MDa class II BCR complex composed of the BamBCDEGHI subunits has so far only been isolated from the Fe(III)‐respiring Geobacter metallireducens . It is supposed to drive endergonic benzene ring reduction at an active site W‐pterin cofactor by flavin‐based electron bifurcation. Here, we identified multiple copies of putative genes encoding the structural components of a class II BCR in sulfate reducing, Fe(III)‐respiring and syntrophic bacteria. A soluble 950 kDa Bam[(BC) 2 DEFGHI] 2 complex was isolated from extracts of Desulfosarcina cetonica cells grown with benzoate/sulfate. Metal and cofactor analyses together with the identification of conserved binding motifs gave rise to 4 W‐pterins, two selenocysteines, six flavin adenine dinucleotides, four Zn, and 48 FeS clusters. The complex exhibited 1,5‐dienoyl‐CoA‐, NADPH‐ and ferredoxin‐dependent oxidoreductase activities. Our results indicate that high‐molecular class II BCR metalloenzyme machineries are remarkably conserved in strictly anaerobic bacteria with regard to subunit architecture and cofactor content, but their subcellular localization and electron acceptor preference may differ as a result of adaptations to variable energy metabolisms.

Genetic differentiation of the Malawi blue crab reflects Pleistocene desiccation of Lake Malawi (Brachyura, Potamonautidae: Potamonautes lirrangensis (Rathbun, 1904)) - John K. Kochey; Savel R. Daniels; Cornelia Plagge; Soudabeh Mehrabi; Lukas Hartmann; Friedemann Schrenk; Martin Plath; Sebastian Klaus (Hydrobiologia, 2019)

Myositis in Lewis rats induced by the superantigen Staphylococcal enterotoxin A - Alexander Emmer; Abimbola Abobarin-Adeagbo; Andreas Posa; Berit Jordan; Karl-Stefan Delank; Martin Sebastian Staege; Alexander Surov; Stephan Zierz; Malte Erich Kornhuber (Molecular Biology Reports, 2019)

Correction to: Liming in spruce stands: What effect does the number of lime applications have on the herb layer? - Martin Baumann; Sebastian Dittrich; Michael Körner; Goddert von Oheimb (European Journal of Forest Research, 2019)

Liming in spruce stands: What effect does the number of lime applications have on the herb layer? - Martin Baumann; Sebastian Dittrich; Michael Körner; Goddert von Oheimb (European Journal of Forest Research, 2019)

The relative importance of plant-soil feedbacks for plant-species performance increases with decreasing intensity of herbivory - Johannes Heinze; Nadja K. Simons; Sebastian Seibold; Alexander Wacker; Guntram Weithoff; Martin M. Gossner; Daniel Prati; T. Martijn Bezemer; Jasmin Joshi (Oecologia, 2019)

Identification of human endogenous retrovirus transcripts in Hodgkin Lymphoma cells - Marie Barth; Victoria Gröger; Holger Cynis; Martin Sebastian Staege (Molecular Biology Reports, 2019)

Global wheat production with 1.5 and 2.0°C above pre‐industrial warming - Bing Liu; Pierre Martre; Frank Ewert; John R. Porter; Andy J. Challinor; Christoph Müller; Alex C. Ruane; Katharina Waha; Peter J. Thorburn; Pramod K. Aggarwal; Mukhtar Ahmed; Juraj Balkovič; et al. (Global Change Biology, 2019)
Efforts to limit global warming to below 2°C in relation to the pre‐industrial level are under way, in accordance with the 2015 Paris Agreement. However, most impact research on agriculture to date has focused on impacts of warming >2°C on mean crop yields, and many previous studies did not focus sufficiently on extreme events and yield interannual variability. Here, with the latest climate scenarios from the Half a degree Additional warming, Prognosis and Projected Impacts (HAPPI) project, we evaluated the impacts of the 2015 Paris Agreement range of global warming (1.5 and 2.0°C warming above the pre‐industrial period) on global wheat production and local yield variability. A multi‐crop and multi‐climate model ensemble over a global network of sites developed by the Agricultural Model Intercomparison and Improvement Project (AgMIP) for Wheat was used to represent major rainfed and irrigated wheat cropping systems. Results show that projected global wheat production will change by −2.3% to 7.0% under the 1.5°C scenario and −2.4% to 10.5% under the 2.0°C scenario, compared to a baseline of 1980–2010, when considering changes in local temperature, rainfall, and global atmospheric CO 2 concentration, but no changes in management or wheat cultivars. The projected impact on wheat production varies spatially; a larger increase is projected for temperate high rainfall regions than for moderate hot low rainfall and irrigated regions. Grain yields in warmer regions are more likely to be reduced than in cooler regions. Despite mostly positive impacts on global average grain yields, the frequency of extremely low yields (bottom 5 percentile of baseline distribution) and yield inter‐annual variability will increase under both warming scenarios for some of the hot growing locations, including locations from the second largest global wheat producer—India, which supplies more than 14% of global wheat. The projected global impact of warming

A high gene flow in populations of Amblyomma ovale ticks found in distinct fragments of Brazilian Atlantic rainforest - Gislene F. S. R. Fournier; Adriano Pinter; Renata Santiago; Sebastian Muñoz-Leal; Thiago Fernandes Martins; Marcos Gomes Lopes; Karen D. McCoy; Celine Toty; Mauricio C. Horta; Marcelo B. Labruna; Ricardo A. Dias (Experimental and Applied Acarology, 2019)

Climate change impact and adaptation for wheat protein - Senthold Asseng; Pierre Martre; Andrea Maiorano; Reimund P. Rötter; Garry J. O’Leary; Glenn J. Fitzgerald; Christine Girousse; Rosella Motzo; Francesco Giunta; M. Ali Babar; Matthew P. Reynolds; Ahmed M. S. Kheir; et al. (Global Change Biology, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO 2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO 2 . Introducing genotypes adapted to warmer temperatures (and also considering changes in CO 2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.

Specialisation and diversity of multiple trophic groups are promoted by different forest features - Caterina Penone; Eric Allan; Santiago Soliveres; María R Felipe‐Lucia; Martin M Gossner; Sebastian Seibold; Nadja K. Simons; Peter Schall; Fons van der Plas; Peter Manning; Rubén D. Manzanedo; Steffen Boch; et al. (Ecology Letters, 2019)
While forest management strongly influences biodiversity, it remains unclear how the structural and compositional changes caused by management affect different community dimensions (e.g. richness, specialisation, abundance or completeness) and how this differs between taxa. We assessed the effects of nine forest features (representing stand structure, heterogeneity and tree composition) on thirteen above‐ and belowground trophic groups of plants, animals, fungi and bacteria in 150 temperate forest plots differing in their management type. Canopy cover decreased light resources, which increased community specialisation but reduced overall diversity and abundance. Features increasing resource types and diversifying microhabitats (admixing of oaks and conifers) were important and mostly affected richness. Belowground groups responded differently to those aboveground and had weaker responses to most forest features. Our results show that we need to consider forest features rather than broad management types and highlight the importance of considering several groups and community dimensions to better inform conservation.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Multimodel ensembles improve predictions of crop–environment–management interactions - Daniel Wallach; Pierre Martre; Bing Liu; Senthold Asseng; Frank Ewert; Peter J. Thorburn; Martin van Ittersum; Pramod K. Aggarwal; Mukhtar Ahmed; Bruno Basso; Christian Biernath; Davide Cammarano; et al. (Global Change Biology, 2018)
A recent innovation in assessment of climate change impact on agricultural production has been to use crop multimodel ensembles ( MME s). These studies usually find large variability between individual models but that the ensemble mean (e‐mean) and median (e‐median) often seem to predict quite well. However, few studies have specifically been concerned with the predictive quality of those ensemble predictors. We ask what is the predictive quality of e‐mean and e‐median, and how does that depend on the ensemble characteristics. Our empirical results are based on five MME studies applied to wheat, using different data sets but the same 25 crop models. We show that the ensemble predictors have quite high skill and are better than most and sometimes all individual models for most groups of environments and most response variables. Mean squared error of e‐mean decreases monotonically with the size of the ensemble if models are added at random, but has a minimum at usually 2–6 models if best‐fit models are added first. Our theoretical results describe the ensemble using four parameters: average bias, model effect variance, environment effect variance, and interaction variance. We show analytically that mean squared error of prediction ( MSEP ) of e‐mean will always be smaller than MSEP averaged over models and will be less than MSEP of the best model if squared bias is less than the interaction variance. If models are added to the ensemble at random, MSEP of e‐mean will decrease as the inverse of ensemble size, with a minimum equal to squared bias plus interaction variance. This minimum value is not necessarily small, and so it is important to evaluate the predictive quality of e‐mean for each target population of environments. These results provide new information on the advantages of ensemble predictors, but also show their limitations.

Ecological correlates of the spatial co‐occurrence of sympatric mammalian carnivores worldwide - Courtney L. Davis; Lindsey N. Rich; Zach J. Farris; Marcella J. Kelly; Mario S. Di Bitetti; Yamil Di Blanco; Sebastian Albanesi; Mohammad S. Farhadinia; Navid Gholikhani; Sandra Hamel; Bart J. Harmsen; Claudia Wultsch; et al. (Ecology Letters, 2018)
The composition of local mammalian carnivore communities has far‐reaching effects on terrestrial ecosystems worldwide. To better understand how carnivore communities are structured, we analysed camera trap data for 108 087 trap days across 12 countries spanning five continents. We estimate local probabilities of co‐occurrence among 768 species pairs from the order Carnivora and evaluate how shared ecological traits correlate with probabilities of co‐occurrence. Within individual study areas, species pairs co‐occurred more frequently than expected at random. Co‐occurrence probabilities were greatest for species pairs that shared ecological traits including similar body size, temporal activity pattern and diet. However, co‐occurrence decreased as compared to other species pairs when the pair included a large‐bodied carnivore. Our results suggest that a combination of shared traits and top‐down regulation by large carnivores shape local carnivore communities globally.

The diversity of saproxylic insects (Coleoptera, Heteroptera) on four tree species of the Hyrcanian forest in Iran - Jörg Müller; Hassan Barimani Varandi; Mohammad Reza Babaii; Mohammad Ebrahim Farashiani; Khosro Sageb-Talebi; Frank Lange; Martin M. Gossner; Andrea Jarzabek-Müller; Nicolas Roth; Simon Thorn; Sebastian Seibold (Journal of Insect Conservation, 2018)

Atmospheric feedbacks in North Africa from an irrigated, afforested Sahara - Tronje Peer Kemena; Katja Matthes; Thomas Martin; Sebastian Wahl; Andreas Oschlies (Climate Dynamics, 2018)

Trees tolerate an extreme heatwave via sustained transpirational cooling and increased leaf thermal tolerance - John E. Drake; Mark G. Tjoelker; Angelica Vårhammar; Belinda E. Medlyn; Peter B. Reich; Andrea Leigh; Sebastian Pfautsch; Chris J. Blackman; Rosana López; Michael J. Aspinwall; Kristine Y. Crous; Remko A. Duursma; et al. (Global Change Biology, 2018)
Heatwaves are likely to increase in frequency and intensity with climate change, which may impair tree function and forest C uptake. However, we have little information regarding the impact of extreme heatwaves on the physiological performance of large trees in the field. Here, we grew Eucalyptus parramattensis trees for 1 year with experimental warming (+3°C) in a field setting, until they were greater than 6 m tall. We withheld irrigation for 1 month to dry the surface soils and then implemented an extreme heatwave treatment of 4 consecutive days with air temperatures exceeding 43°C, while monitoring whole‐canopy exchange of CO 2 and H 2 O, leaf temperatures, leaf thermal tolerance, and leaf and branch hydraulic status. The heatwave reduced midday canopy photosynthesis to near zero but transpiration persisted, maintaining canopy cooling. A standard photosynthetic model was unable to capture the observed decoupling between photosynthesis and transpiration at high temperatures, suggesting that climate models may underestimate a moderating feedback of vegetation on heatwave intensity. The heatwave also triggered a rapid increase in leaf thermal tolerance, such that leaf temperatures observed during the heatwave were maintained within the thermal limits of leaf function. All responses were equivalent for trees with a prior history of ambient and warmed (+3°C) temperatures, indicating that climate warming conferred no added tolerance of heatwaves expected in the future. This coordinated physiological response utilizing latent cooling and adjustment of thermal thresholds has implications for tree tolerance of future climate extremes as well as model predictions of future heatwave intensity at landscape and global scales.

The psychoactive drug Escitalopram affects swimming behaviour and increases boldness in zebrafish (Danio rerio) - Sebastian V. Nielsen; Martin Kellner; Per G. Henriksen; Håkan Olsén; Steen H. Hansen; Erik Baatrup (Ecotoxicology, 2018)

Hochauflösendes Monitoring von Karst-Grundwasserressourcen beiderseits des Jordangrabens – Konzepte und Anwendungsbeispiele - Sebastian Schmidt; Felix Grimmeisen; Fabian Ries; Nico Goldscheider; Martin Sauter (Grundwasser, 2018)

Correction to: Improving the baking quality of bread wheat by genomic selection in early generations - Sebastian Michel; Christian Kummer; Martin Gallee; Jakob Hellinger; Christian Ametz; Batuhan Akgöl; Doru Epure; Huseyin Güngör; Franziska Löschenberger; Hermann Buerstmayr (Theoretical and Applied Genetics, 2018)

Improving the baking quality of bread wheat by genomic selection in early generations - Sebastian Michel; Christian Kummer; Martin Gallee; Jakob Hellinger; Christian Ametz; Batuhan Akgöl; Doru Epure; Franziska Löschenberger; Hermann Buerstmayr (Theoretical and Applied Genetics, 2018)

Working memory capacity and the functional connectome - insights from resting-state fMRI and voxelwise centrality mapping - Sebastian Markett; Martin Reuter; Behrend Heeren; Bernd Lachmann; Bernd Weber; Christian Montag (Brain Imaging and Behavior, 2018)

New evidence for the recent divergence of Devil's Hole pupfish and the plausibility of elevated mutation rates in endangered taxa - Christopher H. Martin; Sebastian Höhna (Molecular Ecology, 2018)
Sağlam et al. recently argued that the Devil's Hole pupfish ( Cyprinodon diabolis ), a conservation icon with the smallest known species range, was isolated 60 kya based on a new genomic data set. If true, this would be a radically long timescale for any species to persist at population sizes C. diabolis , ranging from 6.2 to 19.9 kya, overlapping with our previous phylogenetic divergence time estimates of 2.5–6.5 kya. There are many reasons to suspect an even younger age and higher mutation rate in C. diabolis , as we previously estimated, due to their high metabolism, small adult size, small population size and severe environmental stressors. In conclusion, our results highlight the need for measuring mutation rate in this fascinating species and suggest that the ages of endangered taxa present in small, isolated populations may frequently be overestimated.

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Effects of testosterone treatment on hypothalamic neuroplasticity in female-to-male transgender individuals - Georg S. Kranz; Andreas Hahn; Ulrike Kaufmann; Martin Tik; Sebastian Ganger; René Seiger; Allan Hummer; Christian Windischberger; Siegfried Kasper; Rupert Lanzenberger (Brain Structure and Function, 2018)

Prevalence and risk factors associated with Theileria parva infection in cattle in three regions of Tanzania - Isack I. Kerario; Martin C. Simuunza; Sebastian W. Chenyambuga; Marja Koski; Seong-Gu Hwang; Walter Muleya (Tropical Animal Health and Production, 2017)

Contrasting predation pressure of different ground beetles on slugs and their eggs - Sebastian Wendland; Patrick Baudy; Moritz S. Fusser; Martin H. Entling; Jens Schirmel (BioControl, 2017)

Oligomer-prone E57K-mutant alpha-synuclein exacerbates integration deficit of adult hippocampal newborn neurons in transgenic mice - Martin Regensburger; Sebastian R. Schreglmann; Svenja Stoll; Edward Rockenstein; Sandra Loskarn; Wei Xiang; Eliezer Masliah; Beate Winner (Brain Structure and Function, 2017)

Comprehensive analysis of the in vitro and ex ovo hemocompatibility of surface engineered iron oxide nanoparticles for biomedical applications - Florian Schlenk; Sebastian Werner; Martin Rabel; Franziska Jacobs; Christian Bergemann; Joachim H. Clement; Dagmar Fischer (Archives of Toxicology, 2017)

Vernetzen – koordinieren – beraten - Juliane Korn; Günter Rasch; Sebastian Lenz; Anna Hussinger; Martin Schiefelbusch (Standort, 2017)

A primer on systematic reviews in toxicology - Sebastian Hoffmann; Rob B. M. de Vries; Martin L. Stephens; Nancy B. Beck; Hubert A. A. M. Dirven; John R. Fowle; Julie E. Goodman; Thomas Hartung; Ian Kimber; Manoj M. Lalu; Kristina Thayer; Paul Whaley; et al. (Archives of Toxicology, 2017)

Portal branch ligation does not counteract the inhibiting effect of temsirolimus on extrahepatic colorectal metastatic growth - Sebastian Senger; Jens Sperling; Barbara Oberkircher; Martin K. Schilling; Otto Kollmar; Michael D. Menger; Christian Ziemann (Clinical & Experimental Metastasis, 2017)

Lichen secondary metabolites affect growth of Physcomitrella patens by allelopathy - Michal Goga; Sebastian J. Antreich; Martin Bačkor; Wolfram Weckwerth; Ingeborg Lang (Protoplasma, 2017)

Investitionen aus den BRIC-Staaten - Martin Franz; Sebastian Henn (Standort, 2017)

Editorial - Martin Franz; Sebastian Henn (Standort, 2017)

Ketamine-dependent neuronal activation in healthy volunteers - Anna Höflich; Andreas Hahn; Martin Küblböck; Georg S. Kranz; Thomas Vanicek; Sebastian Ganger; Marie Spies; Christian Windischberger; Siegfried Kasper; Dietmar Winkler; Rupert Lanzenberger (Brain Structure and Function, 2017)

Upper Pleistocene cold-water corals from the Inner Sea of the Maldives: taphonomy and environment - Jesús Reolid; Matías Reolid; Christian Betzler; Sebastian Lindhorst; Martin G. Wiesner; Niko Lahajnar (Facies, 2017)

Characterization of chemical-induced sterile inflammation in vitro: application of the model compound ketoconazole in a human hepatic co-culture system - Franziska Wewering; Florent Jouy; Dirk K. Wissenbach; Scarlett Gebauer; Matthias Blüher; Rolf Gebhardt; Ralph Pirow; Martin von Bergen; Stefan Kalkhof; Andreas Luch; Sebastian Zellmer (Archives of Toxicology, 2017)

Tillage system affects fertilizer-induced nitrous oxide emissions - Maike Krauss; Hans-Martin Krause; Simone Spangler; Ellen Kandeler; Sebastian Behrens; Andreas Kappler; Paul Mäder; Andreas Gattinger (Biology and Fertility of Soils, 2017)

Lessons on Climate Sensitivity From Past Climate Changes - Anna S. von der Heydt; Henk A. Dijkstra; Roderik S. W. van de Wal; Rodrigo Caballero; Michel Crucifix; Gavin L. Foster; Matthew Huber; Peter Köhler; Eelco Rohling; Paul J. Valdes; Peter Ashwin; Sebastian Bathiany; et al. (Current Climate Change Reports, 2016)

The future of nemertean taxonomy (phylum Nemertea) — a proposal - Per Sundberg; Sónia C. S. Andrade; Thomas Bartolomaeus; Patrick Beckers; Jörn von Döhren; Daria Krämer; Ray Gibson; Gonzalo Giribet; Alfonso Herrera‐Bachiller; Juan Junoy; Hiroshi Kajihara; Sebastian Kvist; et al. (Zoologica Scripta, 2016)

Freshwater vertebrate metabarcoding on Illumina platforms using double-indexed primers of the mitochondrial 16S rRNA gene - Miguel Vences; Mariana L. Lyra; R. G. Bina Perl; Molly C. Bletz; David Stanković; Carla Martins Lopes; Michael Jarek; Sabin Bhuju; Robert Geffers; Célio F. B. Haddad; Sebastian Steinfartz (Conservation Genetics Resources, 2016)

High decapod diversity revealed by minimal-invasive, short-term survey of Brijuni marine protected area - Roland R. Melzer; Moira Bursic; Feliza Ceseña; Jana S. Dömel; Martin Heß; Sebastian Landmann; Martina Metz; Martin Pfannkuchen; Isaac Reed; Roland Meyer (Biodiversity and Conservation, 2016)

Drivers of nitrogen leaching from organic layers in Central European beech forests - Martin T. Schwarz; Sebastian Bischoff; Stefan Blaser; Steffen Boch; Fabrice Grassein; Bernhard Klarner; Barbara Schmitt; Emily F. Solly; Christian Ammer; Beate Michalzik; Peter Schall; Stefan Scheu; et al. (Plant and Soil, 2016)

Voxelwise eigenvector centrality mapping of the human functional connectome reveals an influence of the catechol-O-methyltransferase val158met polymorphism on the default mode and somatomotor network - Sebastian Markett; Christian Montag; Behrend Heeren; Rayna Saryiska; Bernd Lachmann; Bernd Weber; Martin Reuter (Brain Structure and Function, 2016)

No correlation between NF1 mutation position and risk of optic pathway glioma in 77 unrelated NF1 patients - Sonja Hutter; Rosario M. Piro; Sebastian M. Waszak; Hildegard Kehrer-Sawatzki; Reinhard E. Friedrich; Alvaro Lassaletta; Olaf Witt; Jan O. Korbel; Peter Lichter; Martin U. Schuhmann; Stefan M. Pfister; Uri Tabori; et al. (Human Genetics, 2016)

Effect of muscle length on voluntary activation of the plantar flexors in boys and men - Virginie Kluka; Vincent Martin; Sebastian Garcia Vicencio; Mathias Giustiniani; Claire Morel; Cédric Morio; Emmanuel Coudeyre; Sébastien Ratel (European Journal of Applied Physiology, 2016)

Production of Jumbo Blooms by Semi-continuous Casting: Challenges, Feasibility, and Future Potential - Sebastian Michelic; Martin Riedler (BHM Berg- und Hüttenmännische Monatshefte, 2016)

Pronounced species turnover, but no functional equivalence in leaf consumption of invasive amphipods in the river Rhine - Jonas Jourdan; Benjamin Westerwald; Antonia Kiechle; Wei Chen; Bruno Streit; Sebastian Klaus; Matthias Oetken; Martin Plath (Biological Invasions, 2016)

A Modeling and Simulation Framework for Adverse Events in Erlotinib-Treated Non-Small-Cell Lung Cancer Patients - Ahmed Abbas Suleiman; Sebastian Frechen; Matthias Scheffler; Thomas Zander; Lucia Nogova; Martin Kocher; Ulrich Jaehde; Jürgen Wolf; Uwe Fuhr (The AAPS Journal, 2015)

Obesity-related differences in neuromuscular fatigue in adolescent girls - Sebastian Garcia-Vicencio; Vincent Martin; Virginie Kluka; Charlotte Cardenoux; Anne-Gaëlle Jegu; Anne-Véronique Fourot; Emmanuel Coudeyre; Sébastien Ratel (European Journal of Applied Physiology, 2015)

Optimality in the zonation of ammonia detoxification in rodent liver - Martin Bartl; Michael Pfaff; Ahmed Ghallab; Dominik Driesch; Sebastian G. Henkel; Jan G. Hengstler; Stefan Schuster; Christoph Kaleta; Rolf Gebhardt; Sebastian Zellmer; Pu Li (Archives of Toxicology, 2015)

Abiotic and Biotic Processes Governing the Fate of Phenylurea Herbicides in Soils: A Review - Sabir Hussain; Muhammad Arshad; Dirk Springael; Sebastian R. SøRensen; Gary D. Bending; Marion Devers-Lamrani; Zahid Maqbool; Fabrice Martin-Laurent (Critical Reviews in Environmental Science and Technology, 2015)

Modulation of nicotine effects on selective attention by DRD2 and CHRNA4 gene polymorphisms - Stefan Ahrens; Sebastian Markett; Thomas P. K. Breckel; Oliver Behler; Martin Reuter; Christiane M. Thiel (Psychopharmacology, 2015)

Pharmacodynamic and response surface analysis of linezolid or vancomycin combined with meropenem against Staphylococcus aureus - Sebastian G. Wicha; Martin G. Kees; Janin Kuss; Charlotte Kloft (Pharmaceutical Research, 2015)

Optic radiation structure and anatomy in the normally developing brain determined using diffusion MRI and tractography - Michael Dayan; Monica Munoz; Sebastian Jentschke; Martin J. Chadwick; Janine M. Cooper; Kate Riney; Faraneh Vargha-Khadem; Chris A. Clark (Brain Structure and Function, 2015)

Erratum to: New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2014)

The Role of the BDNF Val66Met Polymorphism in Individual Differences in Long-Term Memory Capacity - Christian Montag; Andrea Felten; Sebastian Markett; Luise Fischer; Katja Winkel; Andrew Cooper; Martin Reuter (Journal of Molecular Neuroscience, 2014)

Torpor at high ambient temperature in a neotropical didelphid, the grey short-tailed opossum (Monodelphis domestica) - Sebastian Busse; Dominik Lutter; Gerhard Heldmaier; Martin Jastroch; Carola W. Meyer (The Science of Nature, 2014)

Discrimination between random and non-random processes in early bacterial colonization on biomaterial surfaces: application of point pattern analysis - Daniel Siegismund; Anja Schroeter; Claudia Lüdecke; Andreas Undisz; Klaus D. Jandt; Martin Roth; Markus Rettenmayr; Stefan Schuster; Sebastian Germerodt (Biofouling, 2014)

Long-term 13C labeling provides evidence for temporal and spatial carbon allocation patterns in mature Picea abies - Manuel Mildner; Martin K.-F. Bader; Sebastian Leuzinger; Rolf T. W. Siegwolf; Christian Körner (Oecologia, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Small range and distinct distribution in a satellite breeding colony of the critically endangered Waved Albatross - Jill A. Awkerman; Sebastian Cruz; Carolina Proaño; Kathryn P. Huyvaert; Gustavo Jiménez Uzcátegui; Andres Baquero; Martin Wikelski; David J. Anderson (Journal of Ornithology, 2014)

Kleine indische Investitionen in Deutschland – - Kai Bollhorn; Martin Franz; Sebastian Henn (Standort, 2014)

Scanning electron microscopic surface analysis of cryoconserved skull bone after decompressive craniectomy - Thomas Beez; Martin Sabel; Sebastian Alexander Ahmadi; Kerim Beseoglu; Hans-Jakob Steiger; Michael Sabel (Cell and Tissue Banking, 2014)

Percentage leaf herbivory across vascular plant species - Martin M. Turcotte; Christina J. M. Thomsen; Geoffrey T. Broadhead; Paul V. A. Fine; Ryan M. Godfrey; Greg P. A. Lamarre; Sebastian T. Meyer; Lora A. Richards; Marc T. J. Johnson (Ecology, 2014)
Herbivory is viewed as a major driver of plant evolution and the most important energy pathway from plants to higher trophic levels. Therefore, understanding patterns of herbivory on plants remains a key focus in evolution and ecology. The evolutionary impacts of leaf herbivory include altering plant fitness, local adaptation, the evolution of defenses, and the diversification of plants as well as natural enemies. Leaf herbivory also impacts ecological processes such as plant productivity, community composition, and ecosystem nutrient cycling. Understanding the impact of herbivory on these ecological and evolutionary processes requires species‐specific, as opposed to community‐level, measures of herbivory. In addition, species‐specific data enables the use of modern comparative methods to account for phylogenetic non‐independence. Although hundreds of studies have measured natural rates of leaf consumption, we are unaware of any accessible compilation of these data. We created such a data set to provide the raw data needed to test general hypotheses relating to plant–herbivore interactions and to test the influence of biotic and abiotic factors on herbivory rates across large spatial scales. A large repository will make this endeavor more efficient and robust. In total, we compiled 2641 population‐level measures for either annual or daily rates of leaf herbivory across 1145 species of vascular plants collected from 189 studies. All damage measures represent natural occurrences of herbivory that span numerous angiosperm, gymnosperm, and fern species. To enable researchers to explore the causes of variation in herbivory and how these might interact, we added information about the study sites including: geolocation, climate classification, habitat descriptions (e.g., seashore, grassland, forest, agricultural fields), and plant trait information concerning growth form and duration (e.g., annual vs. perennial). We also included extensive details of the methodology used to measure leaf damage, including seasons and months of sampling, age of leaves, and the method used to estimate percentage area missing. We anticipate that these data will make it possible to test important hypotheses in the plant–herbivore literature, including the plant apparency hypothesis, the latitudinal‐herbivory defense hypothesis, the resource availability hypothesis, and the macroevolutionary escalation of defense hypothesis.

Mind the gaps when using science to address conservation concerns - Jan Christian Habel; Martin M. Gossner; Sebastian T. Meyer; Hilde Eggermont; Luc Lens; Jürgen Dengler; Wolfgang W. Weisser (Biodiversity and Conservation, 2013)

Methanogenic capabilities of ANME ‐archaea deduced from 13 C ‐labelling approaches - Sebastian Bertram; Martin Blumenberg; Walter Michaelis; Michael Siegert; Martin Krüger; Richard Seifert (Environmental Microbiology, 2013)
Summary Anaerobic methanotrophic archaea ( ANME ) are ubiquitous in marine sediments where sulfate dependent anaerobic oxidation of methane ( AOM ) occurs. Despite considerable progress in the understanding of AOM , physiological details are still widely unresolved. We investigated two distinct microbial mat samples from the B lack S ea that were dominated by either ANME ‐1 or ANME ‐2. The 13 C lipid stable isotope probing ( SIP ) method using labelled substances, namely methane, bicarbonate, acetate, and methanol, was applied, and the substrate‐dependent methanogenic capabilities were tested. Our data provide strong evidence for a versatile physiology of both, ANME ‐1 and ANME ‐2. Considerable methane production rates ( MPRs ) from CO 2 ‐reduction were observed, particularly from ANME ‐2 dominated samples and in the presence of methane, which supports the hypothesis of a co‐occurrence of methanotrophy and methanogenesis in the AOM systems ( AOM / MPR up to 2:1). The experiments also revealed strong methylotrophic capabilities through 13 C ‐assimilation from labelled methanol, which was independent of the presence of methane. Additionally, high MPRs from methanol were detected in both of the mat samples. As demonstrated by the 13 C ‐uptake into lipids, ANME ‐1 was found to thrive also under methane free conditions. Finally, C 35 ‐isoprenoid hydrocarbons were identified as new lipid biomarkers for ANME ‐1, most likely functioning as a hydrogen sink during methanogenesis.

Podoplanin expressing cancer associated fibroblasts are associated with unfavourable prognosis in adenocarcinoma of the esophagus - Sebastian F. Schoppmann; Bettina Jesch; Martin F. Riegler; Florian Maroske; Katrin Schwameis; Gerd Jomrich; Peter Birner (Clinical & Experimental Metastasis, 2013)

Ecological status assessment of European lakes: a comparison of metrics for phytoplankton, macrophytes, benthic invertebrates and fish - Anne Lyche-Solheim; Christian K. Feld; Sebastian Birk; Geoff Phillips; Laurence Carvalho; Giuseppe Morabito; Ute Mischke; Nigel Willby; Martin Søndergaard; Seppo Hellsten; Agnieszka Kolada; Marit Mjelde; et al. (Hydrobiologia, 2013)

Precipitation-driven decrease in wildfires in British Columbia - Andrea Meyn; Sebastian Schmidtlein; Stephen W. Taylor; Martin P. Girardin; Kirsten Thonicke; Wolfgang Cramer (Regional Environmental Change, 2013)

A plant's perspective of extremes: terrestrial plant responses to changing climatic variability - Christopher P.O. Reyer; Sebastian Leuzinger; Anja Rammig; Annett Wolf; Ruud P. Bartholomeus; Antonello Bonfante; Francesca de Lorenzi; Marie Dury; Philipp Gloning; Renée Abou Jaoudé; Tamir Klein; Thomas M. Kuster; et al. (Global Change Biology, 2013)
We review observational, experimental, and model results on how plants respond to extreme climatic conditions induced by changing climatic variability. Distinguishing between impacts of changing mean climatic conditions and changing climatic variability on terrestrial ecosystems is generally underrated in current studies. The goals of our review are thus (1) to identify plant processes that are vulnerable to changes in the variability of climatic variables rather than to changes in their mean, and (2) to depict/evaluate available study designs to quantify responses of plants to changing climatic variability. We find that phenology is largely affected by changing mean climate but also that impacts of climatic variability are much less studied, although potentially damaging. We note that plant water relations seem to be very vulnerable to extremes driven by changes in temperature and precipitation and that heatwaves and flooding have stronger impacts on physiological processes than changing mean climate. Moreover, interacting phenological and physiological processes are likely to further complicate plant responses to changing climatic variability. Phenological and physiological processes and their interactions culminate in even more sophisticated responses to changing mean climate and climatic variability at the species and community level. Generally, observational studies are well suited to study plant responses to changing mean climate, but less suitable to gain a mechanistic understanding of plant responses to climatic variability. Experiments seem best suited to simulate extreme events. In models, temporal resolution and model structure are crucial to capture plant responses to changing climatic variability. We highlight that a combination of experimental, observational, and/or modeling studies have the potential to overcome important caveats of the respective individual approaches.

Macrocerebellum: Significance and Pathogenic Considerations - Andrea Poretti; Volker Mall; Martin Smitka; Sebastian Grunt; Sarah Risen; Sandra P. Toelle; Jane E. Benson; Shoko Yoshida; Nikolai H. Jung; Sigrid Tinschert; Teresa M. Neuhann; Anita Rauch; et al. (The Cerebellum, 2012)

Linking environmental processes to the in situ functioning of microorganisms by high‐resolution secondary ion mass spectrometry (NanoSIMS) and scanning transmission X‐ray microscopy (STXM) - Sebastian Behrens; Andreas Kappler; Martin Obst (Environmental Microbiology, 2012)
Summary Environmental microbiology research increasingly focuses on the single microbial cell as the defining entity that drives environmental processes. The interactions of individual microbial cells with each other, the environment and with higher organisms shape microbial communities and control the functioning of whole ecosystems. A single‐cell view of microorganisms in their natural environment requires analytical tools that measure both cell function and chemical speciation at the submicrometre scale. Here we review the technical capabilities and limitations of high‐resolution secondary ion mass spectrometry (NanoSIMS) and scanning transmission (soft) X‐ray microscopy (STXM) and give examples of their applications. Whereas NanoSIMS can be combined with isotope‐labelling, thereby localizing the distribution of cellular activities (e.g. carbon/nitrogen fixation/turnover), STXM provides information on the location and chemical speciation of metabolites and products of redox reactions. We propose the combined use of both techniques and discuss the technical challenges of their joint application. Both techniques have the potential to enhance our understanding of cellular mechanisms and activities that contribute to microbially mediated processes, such as the biogeochemical cycling of elements, the transformation of contaminants and the precipitation of mineral phases.

New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2012)

Switching from enoxaparin to dabigatran etexilate: pharmacokinetics, pharmacodynamics, and safety profile - Andreas Clemens; Joanne van Ryn; Regina Sennewald; Norio Yamamura; Joachim Stangier; Martin Feuring; Sebastian Härtter (European Journal of Clinical Pharmacology, 2012)

Urinary bladder cancer risk in relation to a single nucleotide polymorphism (rs2854744) in the insulin-like growth factor-binding protein-3 (IGFBP3) gene - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Expression of multiple membrane-associated phospholipase A1 beta transcript variants and lysophosphatidic acid receptors in Ewing tumor cells - Benjamin Joachim Schmiedel; Christoph Hutter; Manuela Hesse; Martin Sebastian Staege (Molecular Biology Reports, 2011)

Effects of two different dosing regimens of terlipressin on organ functions in ovine endotoxemia - Matthias Lange; Christian Ertmer; Sebastian Rehberg; Andrea Morelli; Gabriele Köhler; Tim G. Kampmeier; Hugo Van Aken; Martin Westphal (Inflammation Research, 2011)

Down-regulation of achaete-scute complex homolog 1 (ASCL1) in neuroblastoma cells induces up-regulation of insulin-like growth factor 2 (IGF2) - Jialing Li; Ingo Neumann; Ines Volkmer; Martin Sebastian Staege (Molecular Biology Reports, 2011)

Fast filtration for metabolome sampling of suspended animal cells - Martin Volmer; Stefan Northoff; Sebastian Scholz; Tobias Thüte; Heino Büntemeyer; Thomas Noll (Biotechnology Letters, 2011)

Nuclear and incommensurate magnetic structure of NaFeGe2O6 between 5 K and 298 K and new data on multiferroic NaFeSi2O6 - Günther J. Redhammer; Anatoliy Senyshyn; Martin Meven; Georg Roth; Sebastian Prinz; Astrid Pachler; Gerold Tippelt; Clemens Pietzonka; Werner Treutmann; Markus Hoelzel; Björn Pedersen; Georg Amthauer (Physics and Chemistry of Minerals, 2011)

Revisiting the anatomy of the central nervous system of a hemimetabolous model insect species: the pea aphid Acyrthosiphon pisum - Martin Kollmann; Sebastian Minoli; Joël Bonhomme; Uwe Homberg; Joachim Schachtner; Denis Tagu; Sylvia Anton (Cell and Tissue Research, 2011)

Dangerous attraction: phagocyte recruitment and danger signals of apoptotic and necrotic cells - Christoph Peter; Sebastian Wesselborg; Martin Herrmann; Kirsten Lauber (Apoptosis, 2010)

The variability of European floods since AD 1500 - Rüdiger Glaser; Dirk Riemann; Johannes Schönbein; Mariano Barriendos; Rudolf Brázdil; Chiara Bertolin; Dario Camuffo; Mathias Deutsch; Petr Dobrovolný; Aryan van Engelen; Silvia Enzi; Monika Halíčková; et al. (Climatic Change, 2010)

Testing the abundant‐centre hypothesis using intertidal porcelain crabs along the Chilean coast: linking abundance and life‐history variation - Marcelo M. Rivadeneira; Patricio Hernáez; J. Antonio Baeza; Sebastian Boltaña; Mauricio Cifuentes; Cristian Correa; Alejandra Cuevas; Erasmo del Valle; Iván Hinojosa; Niklas Ulrich; Nelson Valdivia; Nelson Vásquez; et al. (Journal of Biogeography, 2010)
Aim The abundant‐centre hypothesis (ACH) is based on the assumption that physiological constraints limit populations at the edges of their distributional range, yet the geographical variation of physiological performance or life‐history traits has rarely been examined. Here we examine the applicability of the ACH in a marine system by testing whether physiological predictions are reflected in large‐scale variations of life‐history traits. Location The Chilean coast (18°–42° S), encompassing more than 2500 km along the Pacific coast of South America. Methods Five porcelain crab species ( Petrolisthes granulosus , Petrolisthes laevigatus, Petrolisthes tuberculatus , Petrolisthes violaceus and Allopetrolisthes angulosus ) were sampled on intertidal boulder beaches at 13 sampling sites. For each species and site we evaluated: (1) relative abundance (density), (2) maximum size, (3) size at maturity, (4) sex ratio, (5) proportion of ovigerous females, and (6) presence of recruits. The shape of the spatial distribution of each trait was evaluated statistically against the prediction of four hypothetical models (normal, ramped‐south, ramped‐north and abundant‐edge). Results The relative abundance and life‐history traits showed different spatial patterns among species. Relative abundance (across sites) was fitted by a normal model in only two species. No model fitted the spatial variation in body size and size at first maturity, which showed a slight but monotonic poleward increase in all species. Sex ratio showed a prominent hump‐shaped pattern, with females prevailing in the centre of the ranges and males dominating towards the range boundaries; this pattern was statistically significant in three of the five studied species. The proportion of ovigerous females showed no clear latitudinal trends, and mature individuals were observed across most of the geographical range of the species. However, recruits tended to be absent towards the southern (poleward) boundaries of the distribution. Main conclusions The ACH does not apply to all species equally. The link between abundance and life‐history traits is complex and variable among the porcelain crab species studied. Overall, the observed patterns were consistent with the idea that equatorward boundaries might be controlled by physiological restrictions mainly affecting adult survival, whereas poleward boundaries might be shaped by limitations in reproductive output and larval survival. Our results underline the importance of incorporating ecological, physiological and life‐history studies in future tests of the ACH.

The effects of copper additives on the quantity and cell viability of adherent Staphylococcus epidermidis in silicone implants - Martin Gosau; Lukas Prantl; Martina Feldmann; Andreas Kokott; Sebastian Hahnel; Ralf Bürgers (Biofouling, 2010)

Interaction of Inhibitor of DNA binding 3 (Id3) with Gut-enriched Krüppel-like factor (GKLF) and p53 regulates proliferation of vascular smooth muscle cells - Kerstin Wassmann; Cornelius F. H. Mueller; Ulrich M. Becher; Christian Werner; Alexander Jung; Sebastian Zimmer; Martin Steinmetz; Georg Nickenig; Sven Wassmann (Molecular and Cellular Biochemistry, 2010)

Organic carbon burial efficiency in lake sediments controlled by oxygen exposure time and sediment source - Sebastian Sobek; Edith Durisch-Kaiser; Roland Zurbrügg; Nuttakan Wongfun; Martin Wessels; Natacha Pasche; Bernhard Wehrli (Limnology and Oceanography, 2009)
We compared the burial efficiency of organic carbon (buried OC: deposited OC) in a diverse set of 27 different sediments from 11 lakes, focusing on the potential effects of organic matter source, oxygen exposure, and protective sorption of OC onto mineral surfaces. Average OC burial efficiency was high (mean 48%), and it was particularly high in sediments receiving high input of allochthonous organic matter (mean 67%). Further, OC burial efficiency was strongly negatively related to the oxygen exposure time, again particularly so in sediments receiving high allochthonous loads. On the other hand, OC burial efficiency was not related to the mineral surface area, which was used as a proxy of the sorption capacity of the mineral phase for OC. The high OC burial efficiency in many lake sediments can thus be attributed to the frequent and significant input of allochthonous organic matter to lakes, as well as to a strong dependence of OC burial efficiency on oxygen exposure time. This study demonstrates that the carbon sink in lake sediments alters the OC export from the continents to the sea and that the fate of OC in lake sediments (burial vs. mineralization to carbon dioxide and methane) is highly sensitive to environmental conditions.

Bacterial growth properties at low optical densities - Maja Novak; Thomas Pfeiffer; Martin Ackermann; Sebastian Bonhoeffer (Antonie van Leeuwenhoek, 2009)

Host‐specificity of environmentally transmitted Mycoplasma ‐like isopod symbionts - Sebastian Fraune; Martin Zimmer (Environmental Microbiology, 2008)
Summary Mycoplasms are known as pathogens of economic and medical interest in plants, animals and man. Here, we show a positive correlation between the presence of Mycoplasma ‐like symbionts in their isopod hosts and survivorship on low‐quality food. Most isopods that survived feeding on a cellulose‐based low‐quality diet for 90 days harboured ‘ Candidatus Hepatoplasma’ in their midgut glands, while those that died within 90 days mostly either harboured no or other bacterial symbionts. We detected ‘ Candidatus Hepatoplasma’ in all but one of the examined species of terrestrial isopods from different habitats and locations, suggesting an evolutionarily ancient association between terrestrial isopods and their Mycoplasma ‐like symbionts. Phylogenetic analyses clustered symbionts from different populations of the same isopod species together, and clearly distinguished between symbionts of different isopod species, indicating host‐specificity of ‘ Candidatus Hepatoplasma’, although a previous study provided evidence for environmental symbiont transmission. Nonetheless, horizontal exchange of symbionts between species may have been possible in evolutionary earlier stages, as suggested by only limited congruency of phylogenetic trees of hosts and symbionts. Another symbiont, ‘ Candidatus Hepatincola porcellionum’, was only detected in midgut glands of the most terrestrial tribe of isopods ( Crinocheta ), suggesting an evolutionarily younger host–symbiont association. This symbiont proved to be negatively correlated with host longevity, even on high‐quality food.

Myrtucommulone from Myrtus communis induces apoptosis in cancer cells via the mitochondrial pathway involving caspase-9 - Irina Tretiakova; Dagmar Blaesius; Lucia Maxia; Sebastian Wesselborg; Klaus Schulze-Osthoff; Jindrich Cinatl; Martin Michaelis; Oliver Werz (Apoptosis, 2008)

Transient simulations, empirical reconstructions and forcing mechanisms for the Mid-holocene hydrological climate in southern Patagonia - Sebastian Wagner; Martin Widmann; Julie Jones; Torsten Haberzettl; Andreas Lücke; Christoph Mayr; Christian Ohlendorf; Frank Schäbitz; Bernd Zolitschka (Climate Dynamics, 2007)

Yersinia YopP-induced apoptotic cell death in murine dendritic cells is partially independent from action of caspases and exhibits necrosis-like features - Sabine Gröbner; Stella E. Autenrieth; Irena Soldanova; Dani S. J. Gunst; Martin Schaller; Erwin Bohn; Steffen Müller; Martin Leverkus; Sebastian Wesselborg; Ingo B. Autenrieth; Stefan Borgmann (Apoptosis, 2006)

Collagen and tenascin-C expression along the migration pathway of mouse primordial germ cells - Mauricio Soto-Suazo; Sebastian San Martin; Telma M. T. Zorn (Histochemistry and Cell Biology, 2004)

Differential expression of glycosaminoglycans and proteoglycans in the migratory pathway of the primordial germ cells of the mouse - Mauricio Soto-Suazo; Sebastian San Martin; Emer S. Ferro; Telma M. Zorn (Histochemistry and Cell Biology, 2002)

Admissions caused by adverse drug events to internal medicine and emergency departments in hospitals: a longitudinal population-based study - Sebastian Schneeweiss; Joerg Hasford; Martin Göttler; Annemarie Hoffmann; Ann-Kathrin Riethling; Jerry Avorn (European Journal of Clinical Pharmacology, 2002)

Modulation of hyaluronan in the migratory pathway of mouse primordial germ cells - Mauricio Soto-Suazo; Paulo A. Abrahamsohn; Jaime Pereda; Sebastian San Martin; Helena B. Nader; Lucia O. Sampaio; Telma M. Zorn (Histochemistry and Cell Biology, 2002)

A method to calculate the cumulative energy demand (CED) of lignite extraction - Michael Röhrlich; Mark Mistry; Per N. Martens; Stefan Buntenbach; Martin Ruhrberg; Matthias Dienhart; Sebastian Briem; Rainer Quinkertz; Zeynel Alkan; Kurt Kugeler (The International Journal of Life Cycle Assessment, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)